Polycarbonate resin composition
By introducing specific structural units into polycarbonate resin and polymerizing by transesterification method, the problem of existing resins losing flexibility and low temperature properties in the improvement of heat resistance and mechanical strength is solved, and the polycarbonate resin composition is realized Multiple performance optimization.
Patent Information
- Application Number
- CN202380050000.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-28
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-14
AI Technical Summary
While improving heat resistance and mechanical strength, existing polycarbonate resins are difficult to maintain softness and low-temperature mechanical strength, and some variants lack heat resistance and molding ability.
By making a polycarbonate resin composition containing carbonate structural units derived from polytrimethylene ether glycol and carbonate structural units derived from specific dihydroxy compounds, and polymerizing by transesterification, the composition is ensured in There is a peak melting point temperature at high temperatures.
The comprehensive performance of the polycarbonate resin composition is achieved with excellent heat resistance, flexibility, mechanical strength, low temperature mechanical strength and rubber elasticity, and is suitable for component manufacturing in various industrial fields.
Smart Images

Figure CN119452035A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polycarbonate resin composition. Specifically, the present invention relates to a polycarbonate resin composition having excellent heat resistance, flexibility, mechanical strength, low-temperature mechanical strength, and rubber elasticity. The present invention also relates to a thermoplastic resin composition comprising the polycarbonate resin composition, and an injection-molded article and an extrusion-molded article of the polycarbonate resin composition or the thermoplastic resin composition. Background Art
[0002] Polycarbonate resins are excellent in mechanical strength, electrical properties, transparency, etc., and are widely used as engineering plastics in various fields such as the electrical / electronic equipment field and the automotive field. However, there are few polycarbonate resins used as elastomers such as polyester-based thermoplastic elastomers and thermoplastic polyurethanes. Through the development of polycarbonate-based thermoplastic elastomers, it is possible to expect further expansion of applications.
[0003] On the other hand, due to concerns about global warming caused by the depletion of petroleum resources and the increase in carbon dioxide emissions, there is a demand for the development of plastics using carbon-neutral plant-derived monomers as raw materials. Under such circumstances, in recent years, polycarbonate resins produced using isosorbide (hereinafter sometimes referred to as "ISB") as a plant-derived raw material have been developed and are beginning to be used for automotive parts, optical uses, and glass replacement uses (see, for example, Patent Documents 1 and 2).
[0004] Patent Document 3 discloses a polycarbonate resin having excellent flexibility, hue, and thermal stability using a compound produced from a plant-derived raw material, and a polycarbonate resin composition having excellent impact resistance and heat resistance by using the compound as an impact resistance modifier. Specifically, Patent Document 3 proposes a copolymerized polycarbonate resin using polytrimethylene ether glycol (hereinafter, sometimes abbreviated as "PO3G") and isosorbide.
[0005] Patent Document 4 discloses a copolymerized polycarbonate resin using a polyoxyalkylene glycol and an alicyclic dihydroxy compound and having excellent heat storage properties, heat resistance, and shape retention properties.
[0006] Patent Document 5 proposes a copolymerized polycarbonate resin that generates little gas, using PO3G and an aromatic dihydroxy compound.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: International Publication No. 2004 / 111106
[0010] Patent Document 2: International Publication No. 2007 / 148604
[0011] Patent Document 3: Japanese Patent Application Publication No. 2021-91900
[0012] Patent Document 4: Japanese Patent Application Publication No. 2021-169606
[0013] Patent Document 5: International Publication No. 2021 / 059884 Summary of the invention
[0014] Problems to be solved by the invention
[0015] The polycarbonate resin of Patent Document 3 has excellent flexibility, but due to copolymerization of polytrimethylene ether glycol, the glass transition temperature is significantly lowered, and the heat resistance is reduced.
[0016] The polycarbonate resin of Patent Document 4 has excellent heat storage properties, but in order to exhibit the heat storage properties, it is necessary to have a melting point peak temperature in a low temperature region, that is, it is necessary to be crystallized, which reduces flexibility and mechanical strength.
[0017] Although the polycarbonate resin of Patent Document 5 generates little gas, the present inventors have investigated and found that the polycarbonate resin has low heat resistance and cannot be molded.
[0018] In order to use a polycarbonate resin as an elastomer as a main component resin, not only flexibility but also heat resistance and mechanical strength are required, and therefore improvement is required.
[0019] Under the above circumstances, an object of the present invention is to provide a polycarbonate resin composition having excellent heat resistance, flexibility, mechanical strength, low-temperature mechanical strength, and rubber elasticity.
[0020] Means for solving problems
[0021] The present inventors have found that a polycarbonate resin composition that meets the above purpose can be obtained by preparing a polycarbonate resin composition that contains a carbonate structural unit derived from polytrimethylene ether glycol and a carbonate structural unit derived from a specific dihydroxy compound and has a melting point peak temperature.
[0022] The gist of the present invention lies in the following [1] to
[21] .
[0023] [1] A polycarbonate resin composition comprising a carbonate structural unit (X) derived from an aliphatic dihydroxy compound (1) represented by the following formula (1) and a carbonate structural unit (Y) derived from a dihydroxy compound (2) satisfying the following requirement I, wherein the polycarbonate resin composition has a melting point peak temperature when the melting point peak temperature is measured by heating at a heating rate of 20°C / min using a differential scanning calorimeter.
[0024] <Requirement I>
[0025] The polycarbonate resin (2) obtained by polymerizing the dihydroxy compound (2) and a carbonate source by an ester exchange method has a melting point peak temperature when the melting point peak temperature is measured by heating at a temperature increase rate of 20° C. / min using a differential scanning calorimeter.
[0026] [Chemistry 1]
[0027]
[0028] (In formula (1), n is an integer greater than or equal to 2.)
[0029] [2] The polycarbonate resin composition according to [1], wherein the content of the carbonate structural unit (X) is 1 wt% to 99 wt% and the content of the carbonate structural unit (Y) is 0.1 wt% to 99 wt% in 100 wt% of all carbonate structural units in the polycarbonate resin composition.
[0030] [3] The polycarbonate resin composition according to [2], wherein the content of the carbonate structural unit (X) is greater than 1 wt% and less than 75 wt%, and the content of the carbonate structural unit (Y) is greater than 25 wt% and less than 99 wt%, in 100 wt% of all carbonate structural units in the polycarbonate resin composition.
[0031] [4] The polycarbonate resin composition according to any one of [1] to [3], wherein the sum of the content of the carbonate structural unit (X) and the content of the carbonate structural unit (Y) in 100 wt% of all carbonate structural units in the polycarbonate resin composition is 90 wt% or more.
[0032] [5] The polycarbonate resin composition according to any one of [1] to [4], wherein the aliphatic dihydroxy compound represented by the formula (1) has a number average molecular weight of 400 or more and 2,900 or less.
[0033] [6] The polycarbonate resin composition according to any one of [1] to [5], wherein, in the measurement of the melting point peak temperature of the requirement I, when the polycarbonate resin (2) obtained by polymerization by an ester exchange method is directly subjected to the measurement of the melting point peak temperature, the polycarbonate resin (2) has a melting point peak temperature.
[0034] [7] The polycarbonate resin composition according to any one of [1] to [6], wherein the polycarbonate resin (2) has a melting point peak temperature of 150° C. to 300° C.
[0035] [8] The polycarbonate resin composition according to any one of [1] to [7], wherein the dihydroxy compound (2) is a dihydroxy compound represented by any one of the following formulas (2) to (6).
[0036] [Chemistry 2]
[0037]
[0038] [9] The polycarbonate resin composition according to any one of [1] to [8], wherein the polycarbonate resin composition has the melting point peak temperature in the range of 150° C. or higher.
[0039]
[10] The polycarbonate resin composition according to any one of [1] to [9], wherein the polycarbonate resin composition has the melting point peak temperature in the range of 240° C. or less.
[0040]
[11] The polycarbonate resin composition according to any one of [1] to
[10] , wherein the dihydroxy compound (2) is a dihydroxy compound represented by the following formula (2).
[0041] [Chemistry 3]
[0042]
[0043]
[12] The polycarbonate resin composition according to
[11] , wherein the number average molecular weight (Mn) (polystyrene equivalent molecular weight) measured by GPC is 10,000 or more and 100,000 or less.
[0044]
[13] The polycarbonate resin composition according to any one of [1] to
[12] , comprising the carbonate structural unit (X) and the carbonate structural unit (Y) in the form of a copolymerized polycarbonate resin.
[0045]
[14] The polycarbonate resin composition according to any one of [1] to
[12] , which is a blend of a polycarbonate resin containing the carbonate structural unit (X) and a polycarbonate resin containing the carbonate structural unit (Y).
[0046]
[15] The polycarbonate resin composition according to any one of [1] to
[14] , wherein the flow value (Q value) measured using a Koka rheometer under the conditions of 240°C and 160 kgf is 3×10 -2 cm 3 / sec or more.
[0047]
[16] The polycarbonate resin composition according to any one of [1] to
[15] , which has a glass transition temperature of 30°C or less when the glass transition temperature is measured by heating at a temperature increase rate of 20°C / min using a differential scanning calorimeter.
[0048]
[17] The polycarbonate resin composition according to any one of [1] to
[16] , wherein the tensile modulus of a sample obtained by hot pressing is 5 MPa to 300 MPa.
[0049]
[18] A thermoplastic resin composition comprising the polycarbonate resin composition according to any one of [1] to
[17] , wherein the content of the polycarbonate resin composition in 100 wt % of the thermoplastic resin composition is 1 wt % to 30 wt %.
[0050]
[19] An injection-molded article obtained by injection molding the polycarbonate resin composition according to any one of [1] to
[17] or the thermoplastic resin composition according to
[18] .
[0051]
[20] An extrusion-molded article obtained by extrusion-molding the polycarbonate resin composition according to any one of [1] to
[17] or the thermoplastic resin composition according to
[18] .
[0052]
[21] The extruded product according to
[20] , wherein the extruded product is a sheet or a film.
[0053] Effects of the Invention
[0054] According to the present invention, a polycarbonate resin composition having excellent heat resistance, flexibility, mechanical strength, low-temperature mechanical strength, and rubber elasticity can be provided.
[0055] The polycarbonate resin composition of the present invention has excellent heat resistance, flexibility, mechanical strength, low-temperature mechanical strength and rubber elasticity, and can be widely used as a material for manufacturing parts in automobiles, electric and electronic materials and other industrial fields. DETAILED DESCRIPTION
[0056] Hereinafter, the present invention will be described in detail with reference to the embodiments and examples. However, the present invention is not limited to the embodiments and examples shown below.
[0057] In this specification, unless otherwise specified, "to" is used to mean that the numerical values described before and after it are included as the lower limit and the upper limit.
[0058] [Polycarbonate resin composition]
[0059] The polycarbonate resin composition of the present invention comprises a carbonate structural unit (X) derived from a polytrimethylene ether glycol (PO3G) which is an aliphatic dihydroxy compound represented by the following formula (1) (hereinafter, sometimes referred to as “carbonate structural unit (X)”), and a carbonate structural unit (Y) derived from a dihydroxy compound (2) satisfying the following requirement I (hereinafter, sometimes referred to as “carbonate structural unit (Y)”). When the melting point peak temperature is measured by heating at a heating rate of 20°C / min using a differential scanning calorimeter, the polycarbonate resin composition has a melting point peak temperature.
[0060] <Requirement I>
[0061] The polycarbonate resin (2) obtained by polymerizing the dihydroxy compound (2) and a carbonate source by an ester exchange method has a melting point peak temperature when the melting point peak temperature is measured by heating at a temperature increase rate of 20° C. / min using a differential scanning calorimeter.
[0062] [Chemistry 4]
[0063]
[0064] (In formula (1), n is an integer greater than or equal to 2.)
[0065] <po3g>
[0066] As PO3G as a raw material of the carbonate structural unit (X), PO3G having a biomass degree of 100% synthesized by condensing 1,3-propanediol produced from a plant-derived raw material is preferably used.
[0067] Whether PO3G or the like is produced from plant-derived resources can be determined, for example, by radiocarbon dating. 14 C) to confirm the concentration.
[0068] The number average molecular weight of PO3G is preferably 400 or more and 2,900 or less. The lower limit of the number average molecular weight of PO3G is more preferably 420 or more, and particularly preferably 450 or more. The upper limit of the number average molecular weight of PO3G is more preferably 2,850 or less, and particularly preferably 2,800 or less. Therefore, n in the above formula (1) is preferably a number that satisfies the number average molecular weight.
[0069] In the polycarbonate resin composition of the present invention, the carbonate structural unit (X) derived from PO3G forms a soft segment, and the carbonate structural unit (Y) derived from the aforementioned dihydroxy compound (2) forms a hard segment, thereby exhibiting flexibility, heat resistance, mechanical strength, and rubber elasticity.
[0070] When the number average molecular weight of PO3G is above the above lower limit, soft segments and hard segments are easily formed, and there is a tendency to easily achieve a balance between heat resistance and flexibility. When the number average molecular weight of PO3G is below the above upper limit, the compatibility with the dihydroxy compound (2) is good, and it is possible to prevent the unfavorable situation such as deterioration of transparency and failure to smoothly perform polymerization due to poor compatibility.
[0071] The number average molecular weight of PO3G can be determined by using 1 The value can be calculated by a measurement method using H-NMR or a method for determining the value of the hydroxyl group of the terminal group.
[0072] <Dihydroxy compound (2)>
[0073] The dihydroxy compound (2) serving as a raw material of the carbonate structural unit (Y) satisfies the following requirement I.
[0074] <Requirement I>
[0075] The polycarbonate resin (2) obtained by polymerizing the dihydroxy compound (2) and a carbonate source by an ester exchange method has a melting point peak temperature when the melting point peak temperature is measured by heating at a temperature increase rate of 20° C. / min using a differential scanning calorimeter.
[0076] In the above-mentioned requirement 1, the method for manufacturing polycarbonate resin (2) by polymerizing dihydroxy compound (2) and carbonate source by ester exchange method can be carried out in the same manner as the melt ester exchange method in the manufacturing method of polycarbonate resin composition of the present invention described later. As the carbonate source used at this time, the carbonate esters exemplified as the carbonate esters in the melt ester exchange method described later can be enumerated.
[0077] The fact that the polycarbonate resin (2) "has a melting point peak temperature" as described above means that the polycarbonate resin (2) "has crystallinity". If the dihydroxy compound (2) can produce a polycarbonate resin (2) having crystallinity, then as described later, a polycarbonate resin composition of the present invention having a melting point peak temperature can be produced, and a polycarbonate resin composition excellent in heat resistance, flexibility, mechanical strength, low-temperature mechanical strength, and rubber elasticity can be provided.
[0078] It should be noted that in the measurement of the melting point peak temperature using a differential scanning calorimeter, with respect to the polycarbonate resin (2), the polycarbonate resin (2) obtained by polymerization using an ester exchange method may be directly subjected to the measurement of the melting point peak temperature, or the melting point peak temperature may be measured on a polycarbonate resin (2) obtained by temporarily dissolving the polycarbonate resin in a solvent and then drying and removing the solvent.
[0079] That is, the polycarbonate resin (2) may have crystallinity itself immediately after production, or may have crystallinity by being dissolved in a solvent after production and then being dried to remove the solvent to allow crystallization.
[0080] The solvent used at this time may be any solvent capable of dissolving the polycarbonate resin (2), and examples thereof include solvents used in the method of mixing the polycarbonate resin (a) and the polycarbonate resin (b) in a solution state described later.
[0081] In addition, the concentration of the polycarbonate resin (2) in the solution and the drying method at this time are not particularly limited.
[0082] In general, the solvent can be removed from the resin solution after the polycarbonate resin (2) is dissolved by leaving the solution at rest for a certain period of time under normal pressure or slightly reduced pressure, or by heating the solution to a boiling point or higher of the solvent under normal pressure or slightly reduced pressure.
[0083] It should be noted that when the polycarbonate resin (2) itself has crystallinity immediately after production (the polycarbonate resin (2) is polymerized by an ester exchange method to obtain the polycarbonate resin (2), and the polycarbonate resin (2) has a melting point peak temperature when it is directly subjected to the measurement of the melting point peak temperature), the crystallinity is higher than when it is dissolved in a solvent after production and the solvent is dried and removed to obtain crystallinity, and therefore it is preferred.
[0084] The melting point peak temperature of the polycarbonate resin (2) is not particularly limited, but is preferably 150°C or higher, more preferably 165°C or higher, further preferably 180°C or higher, and is preferably 300°C or lower, more preferably 260°C or lower, for the same reasons as the melting point peak temperature of the polycarbonate resin composition of the present invention described later.
[0085] When the polycarbonate resin (2) has a plurality of melting point peak temperatures, it is preferred that at least the higher melting point peak temperature be within the above range.
[0086] The melting point peak temperature of the polycarbonate resin (2) is the melting point peak temperature obtained by heating the polycarbonate resin (2) at a heating rate of 20°C / min using a differential scanning calorimeter and measuring the calorific value, and taking the temperature of the top of the melting peak. Specifically, it is measured by the method described in Example 1 described later.
[0087] The dihydroxy compound (2) is not particularly limited as long as it satisfies the above requirement I, and an example thereof includes a dihydroxy compound represented by the following formula (2).
[0088] [Chemistry 5]
[0089]
[0090] The dihydroxy compound represented by the above formula (2) itself has crystallinity when used as the polycarbonate resin (2), and is particularly preferred from the viewpoint of high crystallinity and achieving a balance between heat resistance, flexibility and mechanical strength.
[0091] Furthermore, as the dihydroxy compound (2), an aromatic dihydroxy compound represented by the following formula (II) can also be used.
[0092] [Chemistry 6]
[0093]
[0094] (In formula (II), Z represents a single bond, -O-, -S-, -CR 1 R 2 -. R 1 and R 2 R each independently represents a hydrogen atom, a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, or a substituted or unsubstituted aryl group. 1 With R 2 The alkyl groups may bond to each other to form a ring.)
[0095] As -CR in the above formula (II) 1 R 2 -R 1 , R 2 The substituted or unsubstituted alkyl groups are preferably alkyl groups having 1 to 20 carbon atoms, each of which is independent of the other.
[0096] Specific examples of the alkyl group include the following.
[0097] Methyl, ethyl, n-propyl, n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, n-tridecyl, n-tetradecyl, n-pentadecyl, n-hexadecyl, n-heptadecyl, n-octadecyl, n-nonadecyl, n-eicosyl;
[0098] methylethyl, methylpropyl, methylbutyl, methylpentyl, methylhexyl, methylheptyl, methyloctyl, methylnonyl, methyldecyl, methylundecyl, methyldodecyl, methyltridecyl, methyltetradecyl, methylpentadecyl, methylhexadecyl, methylheptadecyl, methyloctadecyl, methylnonadecyl;
[0099] dimethylethyl, dimethylpropyl, dimethylbutyl, dimethylpentyl, dimethylhexyl, dimethylheptyl, dimethyloctyl, dimethylnonyl, dimethyldecyl, dimethylundecyl, dimethyldodecyl, dimethyltridecyl, dimethyltetradecyl, dimethylpentadecyl, dimethylhexadecyl, dimethylheptadecyl, dimethyloctadecyl;
[0100] trimethylbutyl, trimethylpentyl, trimethylhexyl, trimethylheptyl, trimethyloctyl, trimethylnonyl, trimethyldecyl, trimethylundecyl, trimethyldodecyl, trimethyltridecyl, trimethyltetradecyl, trimethylpentadecyl, trimethylhexadecyl, trimethylheptadecyl;
[0101] Ethylpentyl, ethylhexyl, ethylheptyl, ethyloctyl, ethylnonyl, ethyldecyl, ethylundecyl, ethyldodecyl, ethyltridecyl, ethyltetradecyl, ethylpentadecyl, ethylhexadecyl, ethylheptadecyl, ethyloctadecyl;
[0102] Propylhexyl, propylheptyl, propyloctyl, propylnonyl, propyldecyl, propylundecyl, propyldodecyl, propyltridecyl, propyltetradecyl, propylpentadecyl, propylhexadecyl, propylheptadecyl;
[0103] Butyl hexyl, butyl heptyl, butyl octyl, butyl nonyl, butyl decyl, butyl undecyl, butyl dodecyl, butyl tridecyl, butyl tetradecyl, butyl pentadecyl, butyl hexadecyl:
[0104] When these alkyl groups are bonded to each other to form a ring, they are -CR 1 R 2 -, when unsubstituted, cycloalkylidene groups (preferably cycloalkylidene groups having 4 to 12 carbon atoms) such as cyclopentylidene, cyclohexylidene, cycloheptylidene, cyclododecylidene or adamantylidene can be cited. As substituted groups, groups in which these cycloalkylidene groups are substituted with methyl or ethyl groups can be cited.
[0105] As R 1 and R 2 The aryl group includes phenyl, tolyl, 4-methylphenyl, naphthyl and the like.
[0106] As R 1 , R 2 , preferably each independently includes a hydrogen atom, a methyl group, and an ethyl group, and more preferably a hydrogen atom and a methyl group. 1 , R 2 They are all hydrogen atoms or methyl groups.
[0107] Specific examples of the aromatic dihydroxy compound represented by the above formula (II) include 4,4'-dihydroxydiphenyl ether (hereinafter, sometimes referred to as "DHDE") represented by the following formula (3), bis(4-hydroxyphenylmethane (=bisphenol F)) represented by the following formula (4) (hereinafter, sometimes referred to as "BPF"), 4,4'-thiodiphenol (hereinafter, sometimes referred to as "ThioDP") represented by the following formula (5), and 2,2-bis(4-hydroxyphenyl)propane (=bisphenol A) represented by the following formula (6) (hereinafter, sometimes referred to as "BPA") represented by the following formula (6). The aromatic dihydroxy compounds represented by the following formulas (3) to (5) have crystallinity when they are used as the polycarbonate resin (2). The aromatic dihydroxy compound represented by the following formula (6) generally does not have crystallinity when it is used as the polycarbonate resin (2), but becomes crystallinity by being dissolved in a solvent and then drying and removing the solvent. From the viewpoint of crystallinity, the aromatic dihydroxy compounds represented by the following formulas (3) to (5) are more preferred.
[0108] [Chemistry 7]
[0109]
[0110] <Content Form of Carbonate Structural Unit (X) and Carbonate Structural Unit (Y)>
[0111] The carbonate structural unit (X) and the carbonate structural unit (Y) contained in the polycarbonate resin composition of the present invention are not particularly limited.
[0112] Generally, the carbonate structural unit (X) and the carbonate structural unit (Y) are contained in the polycarbonate resin.
[0113] The polycarbonate resin composition of the present invention may be a polycarbonate resin mixture of a polycarbonate resin containing carbonate structural units (X) and a polycarbonate resin containing carbonate structural units (Y), or may contain a copolymerized polycarbonate resin containing both carbonate structural units (X) and carbonate structural units (Y).
[0114] The polycarbonate resin composition of the present invention may be a mixture of a polycarbonate resin comprising a carbonate structural unit (X) and / or a carbonate structural unit (Y) and a copolymerized polycarbonate resin comprising a carbonate structural unit (X) and a carbonate structural unit (Y).
[0115] The polycarbonate resin composition of the present invention may further contain a polycarbonate resin containing neither the carbonate structural unit (X) nor the carbonate structural unit (Y).
[0116] When the polycarbonate resin composition of the present invention comprises the carbonate structural unit (X) and the carbonate structural unit (Y) in the form of a copolymerized polycarbonate resin comprising the carbonate structural unit (X) and the carbonate structural unit (Y), the polycarbonate resin composition of the present invention is referred to as "polycarbonate resin".
[0117] When the polycarbonate resin composition of the present invention is a mixture of a polycarbonate resin containing carbonate structural units (X) and a polycarbonate resin containing carbonate structural units (Y), it is generally referred to as a "polycarbonate resin composition." The same applies to the other containing forms described above.
[0118] In the present invention, the composition is also comprised of one copolymerized polycarbonate resin containing the carbonate structural unit (X) and the carbonate structural unit (Y), and is referred to as a "polycarbonate resin composition".
[0119] However, in the examples and comparative examples described below, since a single copolymerized polycarbonate resin was produced, it is referred to as a "polycarbonate resin".
[0120] <Content of each carbonate structural unit (X) and carbonate structural unit (Y)>
[0121] In the polycarbonate resin composition of the present invention, the content of the carbonate structural unit (X) (hereinafter, the contents of the carbonate structural units such as the carbonate structural unit (X) and the carbonate structural unit (Y) are expressed as weight percentages relative to 100wt% of the total carbonate structural units in the polycarbonate resin composition) is preferably 1wt% to 99wt%, and the content of the carbonate structural unit (Y) is 0.1wt% to 99wt%.
[0122] By containing 1 wt % to 99 wt % of carbonate structural units (X) and 0.1 wt % to 99 wt % of carbonate structural units (Y), the polycarbonate resin composition of the present invention can have good heat resistance, flexibility, mechanical strength, low-temperature mechanical strength, and rubber elasticity.
[0123] From the viewpoint of flexibility and mechanical strength, the content of the carbonate structural unit (X) in the polycarbonate resin composition of the present invention is preferably 1 wt % or more, more preferably 20 wt % or more, further preferably 25 wt % or more, particularly preferably 27 wt % or more, and especially preferably 35 wt % or more, and the content of the carbonate structural unit (Y) is preferably 99 wt % or less, more preferably 80 wt % or less, further preferably 75 wt % or less, particularly preferably 73 wt % or less, and especially preferably 65 wt % or less.
[0124] From the viewpoint of heat resistance, the content of the carbonate structural unit (X) is preferably 99wt% or less, more preferably 80wt% or less, further preferably 77wt% or less, particularly preferably 75wt% or less, and especially preferably 69wt% or less, and the content of the carbonate structural unit (Y) is preferably 0.1wt% or more, more preferably 20wt% or more, further preferably 23wt% or more, particularly preferably 31wt% or more, and especially preferably 37wt% or more.
[0125] From the viewpoint of more reliably obtaining the effects of heat resistance, flexibility, mechanical strength, low-temperature mechanical strength and rubber elasticity brought about by the carbonate structural units (X) and the carbonate structural units (Y), the sum of the content of the carbonate structural units (X) and the content of the carbonate structural units (Y) in 100 wt % of all the carbonate structural units in the polycarbonate resin composition of the present invention is preferably 70 wt % or more, more preferably 75 wt % or more, and further preferably 90 to 100 wt %.
[0126] In the polycarbonate resin composition of the present invention, as the polytrimethylene ether glycol (PO3G) of the carbonate structural unit (X), one molecular weight grade material may be used, or two or more molecular weight grades may be used. As for the carbonate structural unit (Y), only one type may be included, or two or more types may be included. That is, two or more carbonate structural units (Y) derived from a dihydroxy compound (2) may be included.
[0127] The content of each carbonate structural unit (X) and (Y) in the polycarbonate resin composition of the present invention can be obtained as the ratio of each dihydroxy compound, i.e., PO3G and dihydroxy compound (2) in all dihydroxy compounds used in the manufacture of the polycarbonate resin composition of the present invention. The same applies to other carbonate structural units described later.
[0128] <Other carbonate structural units>
[0129] The polycarbonate resin composition of the present invention may also contain other carbonate structural units other than the carbonate structural unit (X) and the carbonate structural unit (Y), that is, carbonate structural units derived from aromatic or aliphatic dihydroxy compounds other than polytrimethylene ether glycol (PO3G) and the dihydroxy compound (2), within the scope not impairing the purpose of the present invention.
[0130] Regarding other carbonate structural units, they may be included in the form of a copolymerized polycarbonate resin with carbonate structural units (X) and / or carbonate structural units (Y), and a polycarbonate resin composed of other carbonate structural units may also be mixed with a polycarbonate resin containing carbonate structural units (X) and / or carbonate structural units (Y).
[0131] When the polycarbonate resin composition of the present invention contains other carbonate structural units, the content of other carbonate structural units in 100 wt % of all carbonate structural units in the polycarbonate resin composition is preferably 30 wt % or less, more preferably 25 wt % or less, and particularly preferably 10 wt % or less.
[0132] When the polycarbonate resin composition contains other carbonate structural units, it is sometimes possible to obtain improvement effects such as reduced water absorption and improved light resistance from other carbonate structural units. However, if the content is too high, it is possible to damage the effects of the present invention such as improved heat resistance, flexibility, mechanical strength, low-temperature mechanical strength, and rubber elasticity brought about by containing carbonate structural units (X) and carbonate structural units (Y).
[0133] The polycarbonate resin composition of the present invention may contain only one type of other carbonate structural unit, or may contain two or more types.
[0134] <Other ingredients>
[0135] As long as the desired physical properties are not significantly damaged, the polycarbonate resin composition of the present invention can also contain other components as required except containing the polycarbonate resin comprising carbonate structural unit (X) and / or carbonate structural unit (Y). If the example of other components is enumerated, resins other than the polycarbonate resin, the polycarbonate resin, various resin additives, etc. can be enumerated that do not contain the above-mentioned carbonate structural unit (X) and carbonate structural unit (Y).
[0136] Examples of the resin additives include heat stabilizers, antioxidants, release agents, light stabilizers (HALS), flame retardants, antistatic agents, antifogging agents, lubricants, antiblocking agents, flow improvers, plasticizers, dispersants, antibacterial agents, dyes, pigments, and the like.
[0137] The resin additive may be contained alone or in any combination and ratio of two or more.
[0138] As other resins, for example, thermoplastic polyester resins such as polyethylene terephthalate resin, polytrimethylene terephthalate resin, and polybutylene terephthalate resin; styrene resins such as polystyrene resin, high impact polystyrene resin (HIPS), acrylonitrile-styrene copolymer (AS resin), acrylonitrile-styrene-acrylic rubber copolymer (ASA resin), and acrylonitrile-ethylene propylene rubber-styrene copolymer (AES resin); polyolefin resins such as polyethylene resin and polypropylene resin; polyamide resin; polyimide resin; polyetherimide resin; polyurethane resin; polyphenylene ether resin; polyphenylene sulfide resin; polysulfone resin; polymethacrylate resin, etc.
[0139] The other resins may be contained alone or in any combination and ratio of two or more.
[0140] When the polycarbonate resin composition of the present invention is formulated as an additive such as an impact resistance modifier into the thermoplastic resin composition of the present invention described later, the polycarbonate resin composition of the present invention preferably contains a total of 70 wt % or more of carbonate structural units (X) and carbonate structural units (Y) in 100 wt % of the polycarbonate resin composition.
[0141] <Melting Peak Temperature of Polycarbonate Resin Composition>
[0142] When the melting point peak temperature is measured by heating at a temperature increase rate of 20° C. / min using a differential scanning calorimeter, the polycarbonate resin composition of the present invention has a melting point peak temperature, that is, has crystallinity.
[0143] The polycarbonate resin composition "having a melting point peak temperature" as described above means that the polycarbonate resin composition "has crystallinity". It should be noted that in the measurement of the melting point peak temperature using a differential scanning calorimeter, the polycarbonate resin composition is directly subjected to the measurement of the melting point peak temperature, and the case where the melting point peak temperature is measured on a polycarbonate resin composition obtained by drying and removing the solvent after temporarily dissolving the polycarbonate resin in a solvent is excluded.
[0144] By making the polycarbonate resin composition of the present invention have a melting point peak temperature in the above-mentioned melting point peak temperature measurement using a differential scanning calorimeter, good rubber elasticity can be obtained through quasi-crosslinking, thereby providing a polycarbonate resin composition excellent in heat resistance, flexibility, mechanical strength, low-temperature mechanical strength, and rubber elasticity.
[0145] The melting point peak temperature of the polycarbonate resin composition of the present invention is not particularly limited. The polycarbonate resin composition of the present invention is heated at a heating rate of 20°C / min using a differential scanning calorimeter and the heat is measured. The melting point peak temperature obtained by taking the temperature of the top of the melting peak is preferably 150°C or more, more preferably 165°C or more, and further preferably 180°C or more. If the melting point peak temperature is above the above lower limit, the heat resistance is excellent, which is preferred. Regarding the upper limit of the melting point peak temperature of the polycarbonate resin composition of the present invention, from the viewpoint of moldability, it is preferably 240°C or less, and more preferably 230°C or less.
[0146] When the polycarbonate resin composition of the present invention has a plurality of melting point peak temperatures, it is preferred that at least the highest melting point peak temperature exists within the above range.
[0147] The melting point peak temperature of the polycarbonate resin composition of the present invention is specifically measured by the method described in Example 1 described later.
[0148] <Molecular Weight of Polycarbonate Resin Composition>
[0149] The molecular weight of the polycarbonate resin composition of the present invention is preferably 10,000 or more and 100,000 or less based on the number average molecular weight (Mn) (polystyrene conversion molecular weight) measured by GPC (gel permeation chromatography). If the number average molecular weight (Mn) is above the above lower limit, the mechanical properties of the polycarbonate resin composition of the present invention become good, so it is preferred. If the number average molecular weight is below the above upper limit, there is a tendency that the fluidity and moldability of the polycarbonate resin composition of the present invention become good, so it is preferred.
[0150] From such a viewpoint, the number average molecular weight (Mn) of the polycarbonate resin composition of the present invention is more preferably 15,000 or more, more preferably 90,000 or less, and further preferably 80,000 or less. In addition, in the GPC (gel permeation chromatography) measurement, the polycarbonate resin composition that cannot be measured by GPC due to insolubility in the solvent can be evaluated for polymerization degree by the fluidity (Q value) shown below.
[0151] <Flowability (Q value) of polycarbonate resin composition>
[0152] The value (Q value) indicating the fluidity of the polycarbonate resin composition of the present invention, which is an index of moldability, is preferably 3×10 -2 cm 3 / sec or more, more preferably 5×10 -2 cm 3 / sec or more, more preferably 10×10 -2 cm 3 When the Q value is greater than the above lower limit, the fluidity and moldability are excellent. On the other hand, the Q value is preferably 200×10 -2 cm 3 / sec or less, more preferably 190×10 -2 cm 3 / sec or less, more preferably 180×10 -2 cm 3 When the Q value is below the above upper limit, the mechanical strength is excellent.
[0153] <Glass Transition Temperature of Polycarbonate Resin Composition>
[0154] The glass transition temperature of the polycarbonate resin composition of the present invention is not particularly limited. The glass transition temperature of the polycarbonate resin composition of the present invention is preferably 30°C or less, more preferably 20°C or less, and further preferably 10°C or less, when the glass transition temperature is below the above upper limit. The low-temperature mechanical strength and rubber elasticity are excellent. The lower limit of the glass transition temperature of the polycarbonate resin composition of the present invention is not particularly limited, but is usually -100°C or more.
[0155] When the polycarbonate resin composition of the present invention has a plurality of glass transition temperatures, it is preferred that at least a low glass transition temperature exists within the above range.
[0156] <Tensile elastic modulus and elongation at break of polycarbonate resin composition>
[0157] The tensile modulus of the polycarbonate resin composition of the present invention is not particularly limited, but preferably has flexibility of 5 MPa to 300 MPa.
[0158] The elongation at break of the polycarbonate resin composition of the present invention is not particularly limited, but is preferably 80% or more from the viewpoint of mechanical strength.
[0159] The tensile modulus and elongation at break of the polycarbonate resin composition of the present invention are measured by the method described in Example 1 below, using a test sample obtained by hot pressing to obtain a square tablet having a thickness of 0.5 mm and a length and width of 70 mm, and then cutting it with scissors into a sheet having a thickness of 0.5 mm, a length of 70 mm, and a width of 10 mm.
[0160] <Recovery Rate and Tensile Set of Polycarbonate Resin Composition>
[0161] The polycarbonate resin composition of the present invention has no particular limitation on the recovery rate and tensile set, but preferably has rubber elasticity such that the recovery rate is 90% or more and the tensile set is 40% or less.
[0162] The recovery rate and tensile permanent set of the polycarbonate resin composition of the present invention were measured by the method described in Example 1 described later, using a test sample obtained by hot pressing to obtain a square sheet with a thickness of 0.5 mm and a length and width of 70 mm, and then cutting it with scissors into a sheet with a thickness of 0.5 mm, a length of 70 mm, and a width of 10 mm.
[0163] <Biomass Degree of Polycarbonate Resin Composition>
[0164] The biomass content of the polycarbonate resin composition of the present invention is defined as the mass ratio of carbonate structural units synthesized from plant-derived resources in the carbonate structural units contained in the polycarbonate resin composition of the present invention. The biomass content of the polycarbonate resin composition of the present invention is preferably 10 wt % or more, more preferably 25 wt % or more.
[0165] [Method for producing polycarbonate resin composition]
[0166] <Method for producing polycarbonate resin>
[0167] The polycarbonate resin constituting the polycarbonate resin composition of the present invention can be manufactured by known polymerization method in the past, and its polymerization method is not particularly limited. If the example of polymerization method is enumerated, the ring-opening polymerization method of interfacial polymerization method, melt transesterification method, pyridine method, cyclic carbonate compound, solid phase transesterification method of prepolymer etc. can be enumerated. Wherein, preferred melt transesterification method, interfacial polymerization method, more preferably melt transesterification method.Below, particularly preferred method in these methods is specifically described.
[0168] (Melt transesterification method)
[0169] In the melt transesterification method, for example, a transesterification reaction between a carbonate ester and a raw material dihydroxy compound is carried out.
[0170] By using a substance containing PO3G and a dihydroxy compound (2) as a raw material dihydroxy compound, a copolymerized polycarbonate resin containing a carbonate structural unit (X) and a carbonate structural unit (Y) can be produced. By using one of these dihydroxy compounds, a polycarbonate resin containing a carbonate structural unit (X) or a carbonate structural unit (Y) can be produced.
[0171] When producing a polycarbonate resin containing the above-mentioned other carbonate structural units, one or more dihydroxy compounds other than PO3G and the dihydroxy compound (2) may be used.
[0172] The carbonate ester may be, for example, a compound represented by the following formula (7), and examples thereof include aryl carbonates, dialkyl carbonates, dicarbonates of dihydroxy compounds, monocarbonates of dihydroxy compounds, and carbonates of dihydroxy compounds such as cyclic carbonates.
[0173] [Chemistry 8]
[0174]
[0175] In the above formula (7), R 11 and R 12 Each independently represents an alkyl group, an aryl group or an aralkyl group having 1 to 30 carbon atoms which may have a substituent.
[0176] Below, sometimes in R 11 and R 12 When it is an alkyl group or an aralkyl group, it is called a dialkyl carbonate, and when it is an aryl group, it is called a diaryl carbonate.
[0177] Among them, from the viewpoint of reactivity with dihydroxy compounds, R 11 and R 12 Any of them is preferably an aryl group which may have a substituent, and more preferably a diaryl carbonate represented by the following formula (8).
[0178] [Chemistry 9]
[0179]
[0180] In the above formula (8), R 13 and R 14 Each independently represents a halogen atom, a nitro group, a cyano group, an alkyl group having 1 to 20 carbon atoms, an alkoxycarbonyl group having 1 to 20 carbon atoms, a cycloalkyl group having 4 to 20 carbon atoms, or an aryl group having 6 to 20 carbon atoms. p and q each independently represent an integer of 0 to 5.
[0181] As such carbonates, specifically, dialkyl carbonates such as dimethyl carbonate, diethyl carbonate, and di-tert-butyl carbonate, diphenyl carbonate (hereinafter sometimes referred to as "DPC"), bis(4-methylphenyl) carbonate, bis(4-chlorophenyl) carbonate, bis(4-fluorophenyl) carbonate, bis(2-chlorophenyl) carbonate, bis(2,4-difluorophenyl) carbonate, bis(4-nitrophenyl) carbonate, bis(2-nitrophenyl) carbonate, bis(methyl salicylphenyl) carbonate, ditolyl carbonate, etc. may have a substituent. Among them, diphenyl carbonate is preferred.
[0182] These carbonates can be used alone or in combination of two or more.
[0183] The aforementioned carbonate can preferably be substituted with dicarboxylic acid or dicarboxylic acid ester in an amount of less than 50mol%, more preferably less than 30mol%. As representative dicarboxylic acid or dicarboxylic acid ester, terephthalic acid, isophthalic acid, diphenyl terephthalate, diphenyl isophthalate etc. can be enumerated. When substituted with such dicarboxylic acid or dicarboxylic acid ester, polyester carbonate can be obtained.
[0184] The ratio of the raw material dihydroxy compound to the carbonate is arbitrary as long as the desired polycarbonate resin can be obtained. These carbonates are preferably used slightly less or slightly excessively than the raw material dihydroxy compound when polymerized with the dihydroxy compound. That is, the carbonate is preferably 0.95 to 1.30 times the amount (molar ratio) relative to the dihydroxy compound, and more preferably 0.98 to 1.20 times the amount (molar ratio).
[0185] If the molar ratio is too small, the terminal OH groups of the obtained polycarbonate resin increase, and there is a tendency for the thermal stability of the resin to deteriorate. If the molar ratio is too large, the reaction rate of the transesterification decreases, and it is sometimes difficult to produce a polycarbonate resin with a desired molecular weight. Sometimes, the amount of carbonate residue in the resin increases, which causes odor during molding processing and when the molded product is made.
[0186] When polycarbonate resin is manufactured by melt transesterification, a transesterification catalyst is usually used. The transesterification catalyst is not particularly limited, and conventionally known transesterification catalysts can be used. For example, alkali metal compounds and / or alkaline earth metal compounds are preferably used. In addition, basic compounds such as basic boron compounds, basic phosphorus compounds, basic ammonium compounds, and amine compounds can also be used in combination as an auxiliary.
[0187] The transesterification catalyst may be used alone or in combination of two or more in any combination and ratio.
[0188] In the melt transesterification method, the reaction temperature is not particularly limited, but is usually 100 to 300°C.
[0189] The pressure during the reaction is not particularly limited, but is usually a reduced pressure condition of 2 mmHg or less.
[0190] As a specific operation, the melt polycondensation reaction may be carried out under the above-mentioned conditions while removing by-products.
[0191] The polycarbonate resin composition of the present invention is significantly affected by thermal history and oxidation in the presence of an alkali catalyst, resulting in deterioration of the hue. Therefore, the reaction temperature is preferably set to 300° C. or less. In addition, in order to prevent oxygen leakage from the equipment due to excessive decompression, it is preferred to select a decompression condition with a lower limit of about 0.05 mmHg or less.
[0192] The reaction can be carried out in either a batch or continuous manner. In the case of a batch reaction, the order of mixing the reaction substrate (reaction raw materials), catalyst, additives, etc. is arbitrary as long as the desired polycarbonate resin can be obtained, and any appropriate order can be set.
[0193] In the melt transesterification method, a catalyst deactivator may be used as needed. As the catalyst deactivator, any compound that neutralizes the transesterification catalyst may be used. Examples thereof include sulfur-containing acidic compounds and derivatives thereof, phosphorus-containing acidic compounds and derivatives thereof, and the like.
[0194] The catalyst deactivator may be used alone or in combination of two or more in any combination and ratio.
[0195] The amount of the catalyst deactivator used is not particularly limited, but is usually 0.5 equivalents or more, preferably 1 equivalent or more, more preferably 3 equivalents or more, and usually 50 equivalents or less, preferably 10 equivalents or less, more preferably 8 equivalents or less, relative to the above-mentioned transesterification catalyst.
[0196] The amount of the catalyst deactivator used is usually 1 ppm or more and 1000 ppm or less, preferably 500 ppm or less, based on the polycarbonate resin.
[0197] <Method for producing polycarbonate resin composition>
[0198] When the polycarbonate resin composition of the present invention is a mixture of a polycarbonate resin containing carbonate structural units (X) and a polycarbonate resin containing carbonate structural units (Y), or when the polycarbonate resin composition of the present invention is a mixture of a polycarbonate resin containing carbonate structural units (X) and / or carbonate structural units (Y) and a copolymerized polycarbonate resin containing carbonate structural units (X) and carbonate structural units (Y), or when the polycarbonate resin composition of the present invention is a polycarbonate resin composition containing two or more polycarbonate resins such as a mixture further containing a polycarbonate resin containing neither carbonate structural units (X) nor carbonate structural units (Y), there is no particular limitation on the method for producing the polycarbonate resin composition of the present invention by mixing a plurality of polycarbonate resins, for example, two polycarbonate resins, polycarbonate resin (a) and polycarbonate resin (b), and examples thereof include the following methods 1) to 4).
[0199] 1) A method of melt-kneading a polycarbonate resin (a) and a polycarbonate resin (b);
[0200] 2) A method of melt-kneading a molten polycarbonate resin (a) and a molten polycarbonate resin (b);
[0201] 3) A method of mixing the polycarbonate resin (a) and the polycarbonate resin (b) in a solution state;
[0202] 4) A method of dry-blending a polycarbonate resin (a) and a polycarbonate resin (b);
[0203] Each method is described below.
[0204] 1) A method of melt-kneading a polycarbonate resin (a) and a polycarbonate resin (b);
[0205] The particles or powder of the polycarbonate resin (a) and the particles or powder of the polycarbonate resin (b) are melt-kneaded using a mixing device such as a kneader, a twin-screw extruder, or a single-screw extruder. The particles or powder of the polycarbonate resin (a) and the particles or powder of the polycarbonate resin (b) may be mixed in a solid state in advance and then kneaded, or one of them may be melted using the aforementioned mixing device, and then the other polycarbonate resin is added thereto and then kneaded.
[0206] The temperature during kneading is not particularly specified, but is preferably 200° C. or higher, more preferably 220° C. or higher, and further preferably 230° C. or higher. In addition, it is preferably 320° C. or lower, and particularly preferably 300° C. or lower. When the temperature during kneading is low, the polycarbonate resin (a) and the polycarbonate resin (b) are not completely mixed, and when a molded product is manufactured, the hardness and impact resistance may vary, which is not preferred. When the temperature during kneading is too high, the color tone of the polycarbonate resin composition may deteriorate, which is not preferred.
[0207] 2) A method of melt-kneading a molten polycarbonate resin (a) and a molten polycarbonate resin (b);
[0208] The polycarbonate resin (a) in a molten state and the polycarbonate resin (b) in a molten state are mixed using a mixing device such as a stirring tank, a static mixer, a kneader, a twin-screw extruder, a single-screw extruder, etc. At this time, if the polycarbonate resin is obtained by, for example, a melt polymerization method, it can be introduced into the above-mentioned mixing device in a molten state without cooling or solidification.
[0209] 3) A method of mixing the polycarbonate resin (a) and the polycarbonate resin (b) in a solution state;
[0210] This method comprises dissolving a polycarbonate resin (a) and a polycarbonate resin (b) in an appropriate solvent to prepare a solution, mixing the solution, and then isolating the solution as a polycarbonate resin composition.
[0211] Examples of suitable solvents include aliphatic hydrocarbons such as hexane and n-heptane; chlorinated aliphatic hydrocarbons such as dichloromethane, chloroform, carbon tetrachloride, dichloroethane, trichloroethane, tetrachloroethane, dichloropropane, and 1,2-dichloroethylene; aromatic hydrocarbons such as benzene, toluene, and xylene; and substituted aromatic hydrocarbons such as nitrobenzene and acetophenone. Among them, chlorinated hydrocarbons such as dichloromethane and chlorobenzene are preferably used. These solvents may be used alone or as a mixture with other solvents.
[0212] Examples of the mixing apparatus include a stirring tank, a static mixer, etc. The mixing temperature is not particularly limited as long as the polycarbonate resin (a) and the polycarbonate resin (b) are dissolved, and is usually carried out at a temperature not higher than the boiling point of the solvent used.
[0213] 4) A method of dry-blending a polycarbonate resin (a) and a polycarbonate resin (b);
[0214] This is a method in which particles or powders of the polycarbonate resin (a) and particles or powders of the polycarbonate resin (b) are dry-blended using a tumbler, a super mixer, a Henschel mixer, a Nauta mixer or the like.
[0215] Among the above methods 1) to 4), methods 1) and 2) of melt-kneading the polycarbonate resin (a) and the polycarbonate resin (b) and method 4) of dry-blending the polycarbonate resin (a) and the polycarbonate resin (b) are preferred.
[0216] When producing the polycarbonate resin composition, in any of the above methods, a pigment, a dye, a release agent, a heat stabilizer, etc. may be appropriately added within a range not impairing the purpose of the present invention.
[0217] [Thermoplastic resin composition]
[0218] The thermoplastic resin composition of the present invention is a thermoplastic resin composition comprising the above-mentioned polycarbonate resin composition of the present invention.
[0219] From the viewpoint of heat resistance, flexibility, mechanical strength and moldability, the content of the polycarbonate resin composition of the present invention in 100 wt % of the thermoplastic resin composition of the present invention is usually 1 wt % to 30 wt %, preferably 5 wt % to 25 wt %.
[0220] Examples of the thermoplastic resin contained in the thermoplastic resin composition of the present invention other than the polycarbonate resin composition of the present invention include other resins that the polycarbonate resin composition of the present invention may contain. The thermoplastic resin composition of the present invention may contain the additives that the polycarbonate resin composition of the present invention may contain.
[0221] The polycarbonate resin composition of the present invention can be blended into a thermoplastic resin composition and used as a physical property improver such as an impact resistance improver due to its excellent heat resistance, flexibility, mechanical strength and low-temperature mechanical strength.
[0222] As described above, when the polycarbonate resin composition of the present invention is used as an additive such as an impact resistance improver of a thermoplastic resin composition, the polycarbonate resin composition of the present invention preferably contains a total of 70 wt % or more of carbonate structural units (X) and carbonate structural units (Y) in 100 wt % of the polycarbonate resin composition.
[0223] [Molding products]
[0224] When a molded article is produced from the polycarbonate resin composition or thermoplastic resin composition of the present invention, a common extrusion molding machine or injection molding machine is used.
[0225] The molding temperature when molding the polycarbonate resin composition or thermoplastic resin composition of the present invention is preferably 200°C or higher, more preferably 220°C or higher, and further preferably 230°C or higher. It is preferably 320°C or lower, and more preferably 300°C or lower.
[0226] If the molding temperature is too low, the melt viscosity may increase, fluidity may decrease, and moldability may decrease. If the molding temperature is too high, polycarbonate resin composition or thermoplastic resin composition may be colored, and the color tone of the molded article obtained may also deteriorate, which is not preferred. In addition, polycarbonate resin composition containing structural units derived from aliphatic dihydroxy compounds such as carbonate structural units (X) may decompose at high temperatures.
[0227] In the case of injection molding or extrusion molding, a pigment, a dye, a release agent, a heat stabilizer and the like may be appropriately added to the polycarbonate resin composition or the thermoplastic resin composition of the present invention within a range not impairing the object of the present invention.
[0228] <Injection molded products>
[0229] When an injection-molded article is produced from the polycarbonate resin composition or thermoplastic resin composition of the present invention, a common injection molding machine is used.
[0230] When using an injection molding machine or the like, the mold temperature is preferably 120° C. or lower, more preferably 90° C. or lower. Also, it is preferably 20° C. or higher, more preferably 30° C. or higher.
[0231] If the mold temperature is too high, the cooling time during molding needs to be extended, the production cycle of the molded product becomes longer, and sometimes the productivity decreases. If the mold temperature is too low, the melt viscosity of the polycarbonate resin composition or the thermoplastic resin composition becomes too high, and there is a possibility that a uniform molded product cannot be obtained, and the molded product surface may be uneven, which is not preferred.
[0232] <Extrusion molding>
[0233] When the extrusion molding product is manufactured from the polycarbonate resin composition or thermoplastic resin composition of the present invention, a conventional extrusion molding machine is used. The extrusion molding machine is generally equipped with a T-die head, a round die head, etc., and extrusion molding products of various shapes can be obtained. As the extrusion molding product, a sheet, a film, a plate, a tube (tube), a pipe (pipe), etc. can be cited. Among them, a sheet or a film is preferred.
[0234] In the extrusion molded product of the polycarbonate resin composition or thermoplastic resin composition of the present invention, in order to improve adhesion, coating properties, and printability, a hard coating layer may be laminated on both sides or one side of the extrusion molded product, or a weather resistance and / or scratch resistance improving film may be thermally laminated on both sides or one side of the extrusion molded product. In addition, embossing, translucent and opaque processing and other treatments may also be implemented on the surface.
[0235] <Purpose>
[0236] The molded article of the polycarbonate resin composition or thermoplastic resin composition of the present invention has excellent heat resistance, flexibility, mechanical strength, low-temperature mechanical strength and rubber elasticity and can be used in buildings, vehicles, electric / electronic equipment, machinery and other various fields.
[0237] Example
[0238] Hereinafter, the present invention will be described in more detail based on examples. However, the present invention is not limited to the following examples.
[0239] [Measurement and evaluation methods]
[0240] The physical properties of the polycarbonate resins obtained in the following Examples and Comparative Examples were measured and evaluated by the following methods.
[0241] (1) Number average molecular weight (Mn), weight average molecular weight (Mw), Mw / Mn
[0242] The number average molecular weight (Mn), the weight average molecular weight (Mw) (molecular weight in terms of polystyrene), and Mw / Mn were determined by GPC (gel permeation chromatography). The details are shown below.
[0243] Column: Plgel 10 μm Guard 50×7.5 mm, Plgel 10 μm MIXED-B 300×7.5 mm (manufactured by Agilent)
[0244] Column temperature concentration: 40℃
[0245] Eluent: Chloroform
[0246] Analysis time: 22.5min
[0247] Detection method: RID
[0248] Injection volume: 20 μL
[0249] Calibration method: Polystyrene conversion
[0250] Calibration curve approximation: cubic formula
[0251] (2) Q value
[0252] As an evaluation of fluidity, the flow value (Q value) of the resin was evaluated. The measurement was performed using a CFT-500EX flow tester manufactured by Shimadzu Corporation, using an aperture of The die head is 10 mm long and the test temperature is 220°C and 240°C, and the test force is 160 kg / cm 2 , the amount of molten resin discharged under the condition of preheating time of 180 seconds (unit: ×10 -2 cm 3 / sec). The Q value is an index of melt viscosity. If they are equal, they have equal moldability. It should be noted that when the melting point peak temperature exceeds 220°C, only the measurement at 240°C is performed.
[0253] (3) Glass transition temperature (Tg), melting point peak temperature (Tm)
[0254] The measurement was performed using a differential scanning calorimeter (DSC6220 manufactured by SII). The obtained polycarbonate resin was used as a measurement sample without drying. An aluminum sample pan containing about 10 mg of the measurement sample was heated from 30°C to 300°C at a heating rate of 20°C / min at a nitrogen flow rate of 50 mL / min, and then cooled to -120°C at a cooling rate of 40°C / min. Then, the temperature was raised to 300°C again at a heating rate of 20°C / min.
[0255] The differential scanning calorimetry curve obtained in the second temperature increase was used as the measurement curve for analysis. The analysis of the glass transition temperature (Tg) and the melting peak temperature (Tm) was performed in accordance with JIS K7121-1987.
[0256] The temperature of the intersection of the straight line obtained by extending the baseline on the low temperature side to the high temperature side and the tangent line drawn at the point where the gradient of the curve of the step-shaped change part of the glass transition reaches the maximum is obtained, that is, the extrapolated glass transition start temperature. The extrapolated glass transition start temperature is taken as the glass transition temperature (Tg). In addition, the melting point peak temperature (Tm) is set as the top of the melting point peak temperature.
[0257] The case where the top of the melting point peak temperature or the glass transition temperature is not detected is defined as "nd". The lower the glass transition temperature (Tg), the higher the low-temperature characteristics are, and the higher the melting point peak temperature (Tm), the higher the heat resistance is.
[0258] (4) Heating test
[0259] About 0.5 g of the obtained polycarbonate resin was placed in an aluminum pan, put into a hot air dryer, and heated at 120°C for 2 hours. After heating, if the sample did not deform, it was judged as "○", and if the sample melted or partially melted and adhered to the aluminum pan, it was judged as "×". If it was "○", it was judged to be high in heat resistance.
[0260] (5) Tensile elastic modulus, elongation at break
[0261] The obtained polycarbonate resin was dried at 70-80°C for more than 3 hours, and about 3 g of the polycarbonate resin was subjected to a preheating of 1-3 minutes and a pressure of 1-5 MPa for 1 minute using a SUS gasket having a thickness of 0.5 mm, a length of 70 mm, and a width of 70 mm using a hot press at a hot pressing temperature of 200-240°C (Comparative Example 6 was performed at 285°C due to its high melting point), and then the gasket was taken out and cooled at room temperature to prepare a 0.5 mm thick pressed sheet. The pressed sheet was cut with scissors into a thickness of 0.5 mm, a length of 70 mm, and a width of 10 mm to obtain a long strip test sample.
[0262] For the obtained test sample, a table-type precision universal testing machine AUTOGRAPH AGS-X (manufactured by Shimadzu Corporation) was used to perform a tensile test with an initial chuck distance of 45 mm and a tensile speed of 50 mm / min to measure the tensile modulus and elongation at break. The lower the tensile modulus, the better the flexibility. The higher the elongation at break, the better the mechanical strength.
[0263] (6) Test piece bending test
[0264] The pressed sheet obtained by the hot pressing was alternately given 5 convex folds and 5 concave folds, a total of 10 folds. If there was no breakage during the 10 folds, it was rated as "A", if there was a breakage or a notch between the 2nd to 10th folds, it was rated as "B", and if there was a breakage or a notch during the first convex fold, it was rated as "C". If it was A or B, it was judged to have high mechanical strength.
[0265] (7) Izod impact strength
[0266] A small injection molding machine (Sellbic C, Mobile, Ltd.) was used to mold a polycarbonate resin sample with a thickness of 3.2 mm, a length of 53.5 mm, and a width of 12.7 mm under the conditions of the barrel temperature and mold temperature described in each example to obtain a test piece. For this test piece, a cutting notch was made at a position 31.8 mm from the end in the longitudinal direction with a notch tip radius of 0.25 mm and a notch depth of 2.54 mm in accordance with ASTM D256, and a notched Izod impact test was performed 5 times at room temperature (23°C) and low temperature (-20°C) using a universal impact tester (Toyo Seiki Seisaku-sho, Ltd.). The case where no fracture occurred in the 5 tests was recorded as "NB".
[0267] (8) Recovery speed and tensile permanent deformation
[0268] A long strip test sample was prepared from the obtained polycarbonate resin in the same manner as in the case of measuring the tensile elastic modulus and the elongation at break.
[0269] Use a desktop precision universal testing machine AUTOGRAPH AGS-X (manufactured by Shimadzu Corporation) to stretch the obtained test sample with an initial distance between chucks (distance between markings) of 45mm and a tensile speed of 50mm / min. Stop when it is stretched to about 100% and keep it for 10 minutes. In addition, measure the distance between markings during holding. Then, shrink it to the initial distance between markings, take out the test sample, and measure the distance between markings of the test sample just after it is taken out (within 30 seconds) and the distance between markings 30 minutes after it is taken out. Using these measured values, calculate the elongated length (A), the recovery length (B) just after it is taken out, and the recovery length (C) 30 minutes after it is taken out, and calculate the recovery speed and tensile permanent deformation. It should be noted that the calculation formulas for the recovery speed and tensile permanent deformation are as follows.
[0270] Recovery speed: {(B) / (C)}×100(%)
[0271] Tensile permanent deformation (%): {((A)-(C)) / (A)}×100(%)
[0272] A larger recovery rate and a smaller tensile set mean that the rubber elasticity is better, which is preferred.
[0273] [raw materials]
[0274] The compounds used in the following Examples and Comparative Examples are described by the following abbreviations. In addition, the compounds used were those of the following manufacturers.
[0275] It should be noted that, among the following compounds, PO3G and ISB use plant-derived raw materials.
[0276] <Dihydroxy Compounds>
[0277] PO3G500-1: polytrimethylene ether glycol, number average molecular weight 562 (manufactured by ALLESSA, trade name: VELVETOL)
[0278] PO3G500-2: polytrimethylene ether glycol, number average molecular weight 514 (manufactured by ALLESSA, trade name: VELVETOL)
[0279] PO3G1000-1: polytrimethylene ether glycol, number average molecular weight 1042 (manufactured by ALLESSA, trade name: VELVETOL)
[0280] PO3G1000-2: polytrimethylene ether glycol, number average molecular weight 1069 (manufactured by ALLESSA, trade name: VELVETOL)
[0281] PO3G2700: polytrimethylene ether glycol, number average molecular weight 2743 (manufactured by ALLESSA, trade name: VELVETOL)
[0282] PTMG3000: polytetramethylene ether glycol, number average molecular weight 2841 (manufactured by Mitsubishi Chemical Corporation)
[0283] PTMG4000: polytetramethylene ether glycol, number average molecular weight 3860 (manufactured by Mitsubishi Chemical Corporation)
[0284] SPG: Spiroglycol (Mitsubishi Gas Chemical Co., Ltd.)
[0285] ISB: Isosorbide (manufactured by Roquette Freres)
[0286] CHDM: 1,4-cyclohexanedimethanol (produced by SK Chemical)
[0287] DHDE: 4,4'-dihydroxydiphenyl ether (manufactured by Tokyo Chemical Industry Co., Ltd.)
[0288] BPF: Bis(4-hydroxyphenylmethane (= bisphenol F) (manufactured by Tokyo Chemical Industry Co., Ltd.)
[0289] ThioDP: 4,4'-thiodiphenol (manufactured by Tokyo Chemical Industry Co., Ltd.)
[0290] BPA: 2,2-bis(4-hydroxyphenyl)propane (= bisphenol A) (manufactured by Mitsubishi Chemical Corporation)
[0291] <Carbonate>
[0292] DPC: diphenyl carbonate (manufactured by Mitsubishi Chemical Corporation)
[0293] <Polymerization Catalyst>
[0294] Calcium acetate monohydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)
[0295] Cesium carbonate (manufactured by Kishida Chemical Co., Ltd.)
[0296] [Measurement of Melting Peak Temperature of Dihydroxy Compound (2)]
[0297] As dihydroxy compounds, only the compounds shown in Table 1 were used, and polycarbonate resins (corresponding to polycarbonate resin (2)) containing 100 wt% of carbonate structural units (Y) were respectively manufactured by the polymerization method described later, and their melting point peak temperatures were measured. Regarding the measurement method, the measurement was performed using the aforementioned method except that the temperature was lowered to 50°C instead of -120°C at any cooling rate of 10 to 40°C / min. The results are shown in Table 1. Regarding its melting point peak temperature, when it has a melting point peak temperature when measured at any cooling rate of 10 to 40°C / min, the polycarbonate resin (2) is judged to have a melting point peak temperature (generally, the slower the cooling rate, the easier it is to detect the melting point peak temperature).
[0298] For BPA only, a polycarbonate resin containing 100 wt% of carbonate structural units (Y) of BPA was dissolved in dichloromethane and dried to measure the melting point peak temperature. The results are shown in Table 1. For the product obtained by dissolving the resin and then drying it, the melting point peak temperature was measured at the first temperature increase.
[0299] [Table 1]
[0300] Types of dihydroxy compounds (2) Melting point peak temperature (℃) SPG 252 DHDE 238 BPF 217,230 ThioDP 218 BPA 242
[0301] As can be seen from Table 1, the compounds used as the dihydroxy compound (2) in the examples all have melting point peak temperatures.
[0302] [Polymerization method]
[0303] A general polymerization method for obtaining a polycarbonate resin (2) by polymerizing a dihydroxy compound (2) and a carbonate source by an ester exchange method is as follows.
[0304] In a glass reactor with a capacity of 570 mL equipped with a reactor stirrer, a reactor heating device, and a reactor pressure regulating device, a dihydroxy compound (2), DPC, and an aqueous solution of cesium carbonate or calcium acetate monohydrate as a catalyst were added so that the amount was any one of 0.5 to 100 μmol relative to 1 mol of the total dihydroxy compound to prepare a raw material mixture. In addition, the ratio of the amount of DPC to the dihydroxy compound (2) was any one of 1.00 to 1.08.
[0305] Next, the pressure in the glass reactor was reduced to 1.3-4.0 kPa (10-30 Torr), and then the operation of returning to atmospheric pressure with nitrogen was repeated 5 times to replace the interior of the reactor with nitrogen. After nitrogen replacement, the external temperature of the reactor (called the front stage polymerization temperature) was set to 220°C, and the internal temperature of the reactor was slowly raised to dissolve the mixture. Then, the stirrer was rotated at 100 rpm. Then, while distilling off the phenol produced as a by-product by the oligomerization reaction of the dihydroxy compound and DPC carried out inside the reactor, the pressure in the reactor was reduced from 101.3 kPa (760 Torr) to 13.3 kPa (100 Torr) by absolute pressure in 40 minutes.
[0306] Next, the pressure in the reactor was maintained at 13.3 kPa, and the ester exchange reaction was carried out for 80 minutes (when the dihydroxy compound (2) was SPG, it was shortened to 45 minutes to prevent solidification caused by crystallization during polymerization) while further distilling off phenol. Then, the temperature outside the reactor (referred to as the second-stage polymerization temperature) was raised to any temperature between 230 and 290° C., and the pressure in the reactor was reduced from 13.3 kPa (100 Torr) to 399 Pa (3 Torr) in absolute pressure gauge over 40 minutes, and the distilled phenol was removed to the outside of the system. Furthermore, the absolute pressure in the reactor was reduced to 60 Pa (about 0.4 Torr) to carry out the polycondensation reaction. When the stirrer of the reactor reached a predetermined stirring power, the polycondensation reaction was terminated. It should be noted that the solubility of crystalline polycarbonate resin in the solvent is poor, and it is difficult to measure the viscosity average molecular weight and adjust the degree of polymerization at the end of the polymerization reaction. Therefore, the degree of polymerization was adjusted with reference to the stirring power.
[0307] In the measurement of the melting point peak temperature of the polycarbonate resin (2), the stirring power is specified to vary depending on the volume of the polymerization tube and the weight of the input raw materials, and is set with reference to the stirring power when the viscosity average molecular weight of the polycarbonate resin (2) is 21,000 when the dihydroxy compound (2) is BPA and the rear-stage polymerization temperature is 290°C under a specific reaction apparatus and a specific input weight.
[0308] Next, the reactor was restored to an absolute pressure of 101.3 kPa with nitrogen gas and then increased to a gauge pressure of 0.2 MPa to extract the polycarbonate resin from the bottom of the reactor in the form of strands. The obtained polycarbonate resin strands were pelletized using a rotary cutter.
[0309] In the above-mentioned polymerization method, the preparation method of each raw material compound of each dihydroxy compound and the subsequent polymerization temperature are as follows.
[0310] [SPG]
[0311] 116.71 g (about 0.383 mol) of SPG, 83.37 g (about 0.389 mol) of DPC and a 3.0 mass % aqueous solution of calcium acetate monohydrate as a catalyst were added so that the amount of calcium acetate monohydrate was 100 μmol per 1 mol of all dihydroxy compounds to prepare a raw material mixture. The second stage polymerization temperature was 285° C. and the polymerization method described above was used.
[0312] [DHDE]
[0313] 116.71 g (about 0.577 mol) of DHDE, 123.64 g (about 0.577 mol) of DPC and a 0.4 mass % aqueous solution of cesium carbonate as a catalyst were added so that the cesium carbonate content was 5 μmol per 1 mol of all dihydroxy compounds to prepare a raw material mixture. The second stage polymerization temperature was 280° C. and the polymerization method described above was used.
[0314] [BPF]
[0315] 116.71 g (about 0.5829 mol) of BPF, 127.98 g (about 0.5974 mol) of DPC and a 0.4 mass % aqueous solution of cesium carbonate as a catalyst were added so that 10 μmol of cesium carbonate was present per 1 mol of all dihydroxy compounds to prepare a raw material mixture. The second stage polymerization temperature was 285° C. and the polymerization method described above was used.
[0316] [ThioDP]
[0317] ThioDP 116.71 g (about 0.5347 mol), DPC 115.69 g (about 0.5401 mol) and a 0.4 mass % aqueous solution of cesium carbonate as a catalyst were added so that cesium carbonate was 10 μmol per 1 mol of all dihydroxy compounds to prepare a raw material mixture. The second stage polymerization temperature was 285° C. and the polymerization method described above was used.
[0318] [BPA]
[0319] 116.71 g (about 0.511 mol) of BPA, 117.18 g (about 0.547 mol) of DPC and a 0.04 mass % aqueous solution of cesium carbonate as a catalyst were added so that the cesium carbonate content was 0.5 μmol per 1 mol of all dihydroxy compounds to prepare a raw material mixture. The second stage polymerization temperature was 290° C. and the polymerization method described above was used.
[0320] [Example 1]
[0321] In a 570 mL glass reactor equipped with a reactor stirrer, a reactor heater, and a reactor pressure regulator, 58.36 g (about 0.0213 mol) of PO3G2700, 58.36 g (about 0.192 mol) of SPG, 46.77 g (about 0.218 mol) of DPC, and a 3.0 wt% aqueous solution of calcium acetate monohydrate as a catalyst were added so that the amount of calcium acetate monohydrate was 300 μmol per 1 mol of all dihydroxy compounds, thereby preparing a raw material mixture.
[0322] Next, the pressure in the glass reactor was reduced to 1.3-4.0 kPa (10-30 Torr), and then the operation of returning to atmospheric pressure with nitrogen was repeated 5 times to replace the interior of the reactor with nitrogen. After nitrogen replacement, the external temperature of the reactor was set to 240°C, and the internal temperature of the reactor was slowly raised to dissolve the mixture. Then, the stirrer was rotated at 100 rpm. Then, the pressure in the reactor was reduced from 101.3 kPa (760 Torr) to 35.3 kPa (265 Torr) by absolute pressure in 30 minutes. Maintain at 35.3 kPa (265 Torr) for 15 minutes, and then reduce the pressure to 13.3 kPa (100 Torr) in 10 minutes. Maintaining at 35.3 kPa and then reducing the pressure to 13.3 kPa is carried out while distilling away the phenol produced as a by-product by the oligomerization reaction of the dihydroxy compound and DPC carried out inside the reactor.
[0323] Next, the pressure in the reactor was maintained at 13.3 kPa, and the phenol was further distilled off while the transesterification reaction was carried out for 80 minutes. Then, the temperature outside the reactor was raised to 260°C, and the pressure in the reactor was reduced from 13.3 kPa (100 Torr) to 399 Pa (3 Torr) by absolute pressure gauge in 40 minutes, and the distilled phenol was removed to the outside of the system. The absolute pressure in the reactor was further reduced to 60 Pa (about 0.4 Torr) to carry out the polycondensation reaction. When the stirrer of the reactor reached the predetermined stirring power, the polycondensation reaction was terminated.
[0324] Next, the polycarbonate resin was extracted from the reactor together with the stirring blade to obtain a polycarbonate resin.
[0325] The polycarbonate resin contains 48.2 wt % of carbonate structural units (X) and 51.8 wt % of carbonate structural units (Y), and has a biomass degree of 47.7 wt %.
[0326] The number average molecular weight (Mn), weight average molecular weight (Mw), Mw / Mn, glass transition temperature (Tg), and melting point peak temperature (Tm) of the polycarbonate resin thus obtained were measured, and a heating test at 120°C was further performed. In addition, a tensile test was performed using a test piece obtained by hot pressing the polycarbonate resin to measure the tensile elastic modulus and elongation at break. In addition, a bending test of the hot pressing test piece was performed. The results are shown in Table 2A.
[0327] [Example 2]
[0328] In a 570 mL glass reactor equipped with a reactor stirrer, a reactor heater, and a reactor pressure regulator, PO3G2700 70.03 g (about 0.0255 mol), SPG 46.68 g (about 0.153 mol), DPC 40.05 g (about 0.187 mol), and a 3.0 wt% aqueous solution of calcium acetate monohydrate as a catalyst were added so that the amount of calcium acetate monohydrate was 100 μmol per 1 mol of all dihydroxy compounds, thereby preparing a raw material mixture.
[0329] Next, the pressure in the glass reactor was reduced to 1.3-4.0 kPa (10-30 Torr), and then the operation of returning to atmospheric pressure with nitrogen was repeated 5 times to replace the interior of the reactor with nitrogen. After nitrogen replacement, the external temperature of the reactor was set to 220°C, and the internal temperature of the reactor was slowly raised to dissolve the mixture. Then, the stirrer was rotated at 100 rpm. After stirring for 60 minutes, the temperature was raised to 240°C, and the phenol produced as a by-product by the oligomerization reaction of the dihydroxy compound and DPC carried out inside the reactor was distilled off, while the pressure in the reactor was reduced from 101.3 kPa (760 Torr) to 13.3 kPa (100 Torr) by absolute pressure in 40 minutes.
[0330] Next, the pressure in the reactor was maintained at 13.3 kPa, and the phenol was further distilled off while the transesterification reaction was carried out for 80 minutes. Then, the temperature outside the reactor was raised to 250°C, and the pressure in the reactor was reduced from 13.3 kPa (100 Torr) to 399 Pa (3 Torr) by absolute pressure gauge in 40 minutes, and the distilled phenol was removed to the outside of the system. Furthermore, the absolute pressure in the reactor was reduced to 40 Pa (about 0.3 Torr) to carry out the polycondensation reaction. When the stirrer of the reactor reached the predetermined stirring power, the polycondensation reaction was terminated.
[0331] Next, the reactor was restored to an absolute pressure of 101.3 kPa with nitrogen gas and then increased to a gauge pressure of 0.2 MPa to extract the polycarbonate resin from the bottom of the reactor in the form of strands. The obtained polycarbonate resin strands were pelletized using a rotary cutter.
[0332] The polycarbonate resin contains 58.2 wt % of carbonate structural units (X) and 41.8 wt % of carbonate structural units (Y), and has a biomass degree of 57.7 wt %.
[0333] The number average molecular weight (Mn), weight average molecular weight (Mw), Mw / Mn, glass transition temperature (Tg), and melting point peak temperature (Tm) of the polycarbonate resin thus obtained were measured, and a heating test at 120° C. was further performed. In addition, a tensile test was performed using a test piece obtained by hot pressing the polycarbonate resin to measure the tensile elastic modulus and elongation at break. In addition, a bending test of the hot pressing test piece was performed.
[0334] Furthermore, using a small injection molding machine (Sellbic C, Mobile, Shinko Co., Ltd.), under the conditions of a barrel temperature of 250°C and a mold temperature of 40°C, a sample with a thickness of 3.2 mm, a length of 53.5 mm, and a width of 12.7 mm was molded, and a notched Izod impact test was performed.
[0335] In addition, a tensile test was performed to determine the recovery rate and tensile permanent set.
[0336] The results are shown in Table 2A, Table 3, and Table 4.
[0337] [Example 3]
[0338] 81.70 g (about 0.0298 mol) of PO3G2700, 35.01 g (about 0.115 mol) of SPG, 32.42 g (about 0.151 mol) of DPC and a 3.0 wt% aqueous solution of calcium acetate monohydrate as a catalyst were added so that the amount of calcium acetate monohydrate was 75 μmol relative to 1 mol of all dihydroxy compounds to prepare a raw material mixture, and the reaction was carried out at 240° C. without raising the external temperature of the reactor at a reduced pressure of 13.3 kPa (100 Torr) to 250° C. The method described in Example 2 was used.
[0339] The obtained polycarbonate resin contained 68.5 wt % of carbonate structural units (X) and 31.5 wt % of carbonate structural units (Y), and had a biomass degree of 67.8 wt %.
[0340] The number average molecular weight (Mn), weight average molecular weight (Mw), Mw / Mn, glass transition temperature (Tg), and melting point peak temperature (Tm) of the polycarbonate resin thus obtained were measured, and a heating test at 120° C. was further performed. In addition, a tensile test was performed using a test piece obtained by hot pressing the polycarbonate resin to measure the tensile elastic modulus and elongation at break. In addition, a bending test of the hot pressing test piece was performed.
[0341] Furthermore, using a small injection molding machine (Sellbic C, Mobile, Shinko Co., Ltd.), under the conditions of a barrel temperature of 240°C and a mold temperature of 40°C, a sample with a thickness of 3.2 mm, a length of 53.5 mm, and a width of 12.7 mm was molded, and a notched Izod impact test was performed.
[0342] In addition, a tensile test was performed to determine the recovery rate and tensile permanent set.
[0343] The results are shown in Table 2A, Table 3, and Table 4.
[0344] [Example 4]
[0345] 58.36 g (about 0.0584 mol) of PO3G1000-1, 58.36 g (about 0.192 mol) of SPG, 55.72 g (about 0.260 mol) of DPC and a 3.0 wt% aqueous solution of calcium acetate monohydrate as a catalyst were added so that the amount of calcium acetate monohydrate was 250 μmol relative to 1 mol of all dihydroxy compounds, and a raw material mixture was prepared. The external temperature of the reactor was increased from 13.3 kPa (100 Torr) when the pressure was reduced to 260° C., and the method described in Example 2 was used except that the above was carried out.
[0346] The obtained polycarbonate resin contained 48.6 wt % of carbonate structural units (X) and 51.4 wt % of carbonate structural units (Y), and had a biomass degree of 47.3 wt %.
[0347] The number average molecular weight (Mn), weight average molecular weight (Mw), Mw / Mn, glass transition temperature (Tg), and melting point peak temperature (Tm) of the polycarbonate resin thus obtained were measured, and a heating test at 120° C. was further performed. In addition, a tensile test was performed using a test piece obtained by hot pressing the polycarbonate resin to measure the tensile elastic modulus and elongation at break. In addition, a bending test of the hot pressing test piece was performed.
[0348] Furthermore, using a small injection molding machine (Sellbic C, Mobile, Shinko Co., Ltd.), under the conditions of a barrel temperature of 250°C and a mold temperature of 40°C, a sample with a thickness of 3.2 mm, a length of 53.5 mm, and a width of 12.7 mm was molded, and a notched Izod impact test was performed.
[0349] In addition, a tensile test was performed to determine the recovery rate and tensile permanent set.
[0350] The results are shown in Table 2A, Table 3, and Table 4.
[0351] [Example 5]
[0352] PO3G500-1 35.01 g (about 0.0623 mol), SPG 81.70 g (about 0.268 mol), DPC 74.03 g (about 0.346 mol) and a 3.0 wt% aqueous solution of calcium acetate monohydrate as a catalyst were added so that the amount of calcium acetate monohydrate was 175 μmol relative to 1 mol of all dihydroxy compounds to prepare a raw material mixture, and the external temperature of the reactor was increased from 13.3 kPa (100 Torr) when the pressure was reduced to 260° C., except that the method described in Example 2 was used.
[0353] The obtained polycarbonate resin contained 29.2 wt % of carbonate structural units (X) and 70.8 wt % of carbonate structural units (Y), and had a biomass degree of 27.8 wt %.
[0354] The number average molecular weight (Mn), weight average molecular weight (Mw), Mw / Mn, glass transition temperature (Tg), and melting point peak temperature (Tm) of the polycarbonate resin thus obtained were measured, and a heating test at 120°C was further performed. In addition, a tensile test was performed using a test piece obtained by hot pressing the polycarbonate resin to measure the tensile elastic modulus and elongation at break. In addition, a bending test of the hot pressing test piece was performed. The results are shown in Table 2A.
[0355] [Example 6]
[0356] PO3G500-1 58.36 g (about 0.104 mol), SPG 58.36 g (about 0.192 mol), DPC 67.12 g (about 0.313 mol) and a 3.0 wt% aqueous solution of calcium acetate monohydrate as a catalyst were added so that the amount of calcium acetate monohydrate was 125 μmol relative to 1 mol of all dihydroxy compounds, and a raw material mixture was prepared, and the reaction was carried out at 240° C. without raising the external temperature of the reactor under reduced pressure of 13.3 kPa (100 Torr) to 250° C. The method described in Example 2 was used. It should be noted that since the strands of the obtained polycarbonate resin were too thin, a rotary cutter could not be used, and the pellets were cut with scissors.
[0357] The obtained polycarbonate resin contained 49.1 wt % of carbonate structural units (X) and 50.9 wt % of carbonate structural units (Y), and had a biomass degree of 46.7 wt %.
[0358] The number average molecular weight (Mn), weight average molecular weight (Mw), Mw / Mn, glass transition temperature (Tg), and melting point peak temperature (Tm) of the polycarbonate resin thus obtained were measured, and a heating test at 120° C. was further performed. In addition, a tensile test was performed using a test piece obtained by hot pressing the polycarbonate resin to measure the tensile elastic modulus and elongation at break. In addition, a bending test of the hot pressing test piece was performed.
[0359] In addition, a tensile test was performed to determine the recovery rate and tensile permanent set.
[0360] The results are shown in Table 2A and Table 4.
[0361] [Comparative Example 1]
[0362] In a 570 mL glass reactor equipped with a reactor stirrer, a reactor heater, and a reactor pressure regulator, 59.63 g (about 0.408 mol) of ISB, 25.22 g (about 0.175 mol) of CHDM, 123.62 g (about 0.577 mol) of DPC, and a 0.2 wt% aqueous solution of calcium acetate monohydrate as a catalyst were added so that the amount of calcium acetate monohydrate was 3 μmol per 1 mol of all dihydroxy compounds, thereby preparing a raw material mixture.
[0363] Next, the pressure in the glass reactor was reduced to 1.3-4.0 kPa (10-30 Torr), and then the operation of returning to atmospheric pressure with nitrogen was repeated 5 times to replace the interior of the reactor with nitrogen. After nitrogen replacement, the external temperature of the reactor was set to 210°C, and the internal temperature of the reactor was slowly raised to dissolve the mixture. Then, the stirrer was rotated at 100 rpm. After stirring for 30 minutes, the phenol produced as a by-product by the oligomerization reaction of the dihydroxy compound and DPC carried out inside the reactor was distilled off, and the pressure in the reactor was reduced from 101.3 kPa (760 Torr) to 13.3 kPa (100 Torr) by absolute pressure in 90 minutes.
[0364] Next, the pressure in the reactor was maintained at 13.3 kPa, and the phenol was further distilled off while the transesterification reaction was carried out for 45 minutes. Then, the temperature outside the reactor was raised to 230°C, and the pressure in the reactor was reduced from 13.3 kPa (100 Torr) to 133 Pa (1 Torr) by absolute pressure gauge in 20 minutes, and the distilled phenol was removed to the outside of the system. Furthermore, the absolute pressure in the reactor was reduced to 50 Pa (about 0.4 Torr) to carry out the polycondensation reaction. When the stirrer of the reactor reached the predetermined stirring power, the polycondensation reaction was terminated.
[0365] Next, the reactor was restored to an absolute pressure of 101.3 kPa with nitrogen gas and then increased to a gauge pressure of 0.2 MPa to extract the polycarbonate resin from the bottom of the reactor in the form of strands. The obtained polycarbonate resin strands were pelletized using a rotary cutter.
[0366] The contents of each carbonate structural unit and the biomass degree of the obtained polycarbonate resin are shown in Table 2B.
[0367] The polycarbonate resin thus obtained was tested for number average molecular weight (Mn), weight average molecular weight (Mw), Mw / Mn, glass transition temperature (Tg), and melting point peak temperature (Tm), and a heating test was performed at 120° C. In addition, a tensile test was performed using a test piece obtained by hot pressing the polycarbonate resin to measure tensile elastic modulus and elongation at break. The results are shown in Table 2B.
[0368] [Comparative Example 2]
[0369] 25.67 g (about 0.176 mol) of ISB, 59.11 g (about 0.410 mol) of CHDM, 124.80 g (about 0.583 mol) of DPC and a 0.2 wt% aqueous solution of calcium acetate monohydrate as a catalyst were added so that the amount of calcium acetate monohydrate was 5 μmol per 1 mol of all dihydroxy compounds to prepare a raw material mixture, and the method described in Comparative Example 1 was followed except that the external temperature of the reactor was increased from 13.3 kPa (100 Torr) when the reduced pressure was reduced to 220° C.
[0370] The contents of each carbonate structural unit and the biomass degree of the obtained polycarbonate resin are shown in Table 2B.
[0371] The number average molecular weight (Mn), weight average molecular weight (Mw), Mw / Mn, glass transition temperature (Tg), and melting point peak temperature (Tm) of the polycarbonate resin thus obtained were measured, and a heating test at 120°C was further performed. In addition, a tensile test was performed using a test piece obtained by hot pressing the polycarbonate resin to measure the tensile elastic modulus and elongation at break. In addition, a bending test of the hot pressing test piece was performed. The results are shown in Table 2B.
[0372] [Comparative Example 3]
[0373] PO3G2700 70.03 g (about 0.0255 mol), ISB 46.68 g (about 0.319 mol), DPC 75.74 g (about 0.354 mol) and a 3.0 wt% aqueous solution of calcium acetate monohydrate as a catalyst were added so that the amount of calcium acetate monohydrate was 50 μmol per 1 mol of all dihydroxy compounds to prepare a raw material mixture, and the reaction was carried out at 240° C. without raising the external temperature of the reactor at a reduced pressure of 13.3 kPa (100 Torr) to 250° C. The method described in Example 2 was used.
[0374] The contents of each carbonate structural unit and the biomass degree of the obtained polycarbonate resin are shown in Table 3B.
[0375] The number average molecular weight (Mn), weight average molecular weight (Mw), Mw / Mn, glass transition temperature (Tg), and melting point peak temperature (Tm) of the polycarbonate resin thus obtained were measured, and a heating test at 120°C was further performed. In addition, a tensile test was performed using a test piece obtained by hot pressing the polycarbonate resin, but the sample was too soft to be measured. In addition, a bending test of the hot pressing test piece was performed. The results are shown in Table 2B.
[0376] It should be noted that there are two glass transition temperatures (Tg). The lower temperature side is considered to be the glass transition temperature derived from the carbonate structural unit composed of PO3G, and the higher temperature side is considered to be the glass transition temperature derived from the carbonate structural unit composed of ISB.
[0377] [Comparative Example 4]
[0378] 55.84 g (about 0.109 mol) of PO3G500-2, 60.87 g (about 0.417 mol) of ISB, 113.62 g (about 0.530 mol) of DPC and a 3.0 wt% aqueous solution of calcium acetate monohydrate as a catalyst were added so that the amount of calcium acetate monohydrate was 140 μmol relative to 1 mol of all dihydroxy compounds to prepare a raw material mixture, and the external temperature of the reactor was raised to 220° C. The same method as described in Comparative Example 1 was used except that the reaction mixture was prepared.
[0379] The contents of each carbonate structural unit and the biomass degree of the obtained polycarbonate resin are shown in Table 3B.
[0380] The number average molecular weight (Mn), weight average molecular weight (Mw), Mw / Mn, glass transition temperature (Tg), and melting point peak temperature (Tm) of the polycarbonate resin thus obtained were measured, and a heating test at 120° C. was further performed. In addition, a tensile test was performed using a test piece obtained by hot pressing the polycarbonate resin to measure the tensile elastic modulus and elongation at break. In addition, a bending test of the hot pressing test piece was performed.
[0381] In addition, a tensile test was performed to determine the recovery rate and tensile permanent set.
[0382] The results are shown in Table 2A and Table 4.
[0383] [Comparative Example 5]
[0384] The method described in Comparative Example 1 was followed except that 76.11 g (about 0.073 mol) of PO3G1000-1, 44.15 g (about 0.302 mol) of ISB, 80.29 g (about 0.375 mol) of DPC and a 3.0 wt% aqueous solution of calcium acetate monohydrate as a catalyst were added so that the amount of calcium acetate monohydrate was 40 μmol relative to 1 mol of all dihydroxy compounds to prepare a raw material mixture.
[0385] The contents of each carbonate structural unit and the biomass degree of the obtained polycarbonate resin are shown in Table 2B.
[0386] The number average molecular weight (Mn), weight average molecular weight (Mw), Mw / Mn, glass transition temperature (Tg), and melting point peak temperature (Tm) of the polycarbonate resin thus obtained were measured, and a heating test at 120° C. was further performed. In addition, a tensile test was performed using a test piece obtained by hot pressing the polycarbonate resin to measure the tensile elastic modulus and elongation at break. In addition, a bending test of the hot pressing test piece was performed.
[0387] In addition, a tensile test was performed to determine the recovery rate and tensile permanent set.
[0388] The results are shown in Table 2A and Table 4.
[0389] [Comparative Example 6]
[0390] PTMG3000 70.03 g (about 0.0233 mol), SPG 46.68 g (about 0.153 mol), DPC 40.05 g (about 0.187 mol) and a 0.4 wt% aqueous solution of cesium carbonate as a catalyst were added so that the amount of cesium carbonate was 30 μmol relative to 1 mol of all dihydroxy compounds, and a raw material mixture was prepared. The external temperature of the reactor was raised from 13.3 kPa (100 Torr) under reduced pressure to 260° C., except that the method described in Example 2 was used. However, crystallization occurred during the polymerization and the stirring power was not increased, so the reaction was stopped.
[0391] Next, the polycarbonate resin was extracted from the reactor together with the stirring blades to obtain a polycarbonate resin. Since the polymerization reaction did not proceed sufficiently, the polycarbonate resin was very brittle.
[0392] The polycarbonate resin contains 58.2 wt % of carbonate structural units (X) and 41.8 wt % of carbonate structural units (Y), and has a biomass degree of 0 wt %.
[0393] The polycarbonate resin thus obtained was attempted to be dissolved in chloroform, but the sample did not dissolve and GPC measurement could not be performed. In addition, the glass transition temperature (Tg) and the melting peak temperature (Tm) were measured, and a heating test at 120° C. was performed. Furthermore, the melting peak temperature of the polycarbonate resin was too high, and polymerization did not proceed sufficiently, so the fluidity when melted by hot pressing was too high, and a sample could not be molded.
[0394] The results are shown in Table 2B.
[0395] It should be noted that there are two melting point peak temperatures (Tm), and it is considered that the lower temperature side is the melting point peak temperature derived from the carbonate structural unit composed of PTMG, and the higher temperature side is the melting point peak temperature derived from the carbonate structural unit composed of SPG.
[0396] [Table 2A]
[0397]
[0398] [Table 2B]
[0399]
[0400] [Table 3]
[0401]
[0402] ※NB means "not broken" 。
[0403] [Table 4]
[0404]
[0405] [Examination of Examples 1 to 6 and Comparative Examples 1 to 6]
[0406] The results of Examples 1 to 6 and Comparative Examples 1 to 6 reveal the following.
[0407] As shown in Table 2A, the polycarbonate resins of Examples 1 to 6 having PO3G (carbonate structural unit (X)) and SPG (carbonate structural unit (Y)) and having a melting point peak temperature all have good results in terms of heat resistance, flexibility, and mechanical strength. In addition, as shown in Table 3, since no fracture was observed in the notched cantilever beam measurement under any of the conditions of 23°C and -20°C, the mechanical strength and low-temperature mechanical strength were good. It is believed that the low-temperature mechanical strength is due to the low glass transition temperature (Tg).
[0408] Furthermore, as can be seen from Table 4, the polycarbonate resin of the present invention has a large recovery rate and a small tensile permanent set, and in particular has a much larger recovery rate than the polycarbonate resin of the comparative example, and is excellent in rubber elasticity.
[0409] On the other hand, as shown in Table 2B, Comparative Examples 1 to 5 do not have a melting point peak temperature, and the heat resistance, flexibility, mechanical strength, and low-temperature mechanical strength are all poor. In Comparative Examples 1 and 2, the copolymerization ratio of ISB to CHDM is changed. If the copolymerization ratio of CHDM is gradually increased, the flexibility is improved, but the glass transition temperature (Tg) gradually decreases, and the heat resistance is reduced. In Comparative Example 1, according to the results of the heating test, the heat resistance is high, but the tensile modulus is high and the flexibility is low. In Comparative Example 2, the following results are obtained: the tensile modulus is reduced compared with Comparative Example 1, the flexibility is improved, but according to the results of the heating test, the heat resistance is low.
[0410] Since Comparative Examples 3 to 5 do not contain the carbonate structural unit (Y), although they have flexibility according to the results of the tensile elastic modulus, according to the results of the heating test, the heat resistance is low, and both heat resistance and flexibility cannot be achieved.
[0411] In addition, it is believed that Comparative Example 6 does not have a carbonate structural unit (X). If PTMG3000 is used, the melting point peak temperature is too high and crystallization occurs during polymerization, and the polymerization reaction cannot proceed smoothly, resulting in a very brittle resin. Although a test sample cannot be obtained by hot pressing, it is believed that the flexibility is low due to being too brittle.
[0412] [Example 7]
[0413] In a 570 mL glass reactor equipped with a reactor stirrer, a reactor heater, and a reactor pressure regulator, 30.00 g (about 0.0111 mol) of PO3G2700, 70.00 g (about 0.346 mol) of DHDE, 77.69 g (about 0.363 mol) of DPC, and a 0.4 wt% aqueous solution of cesium carbonate as a catalyst were added so that the amount of cesium carbonate was 5 μmol per 1 mol of all dihydroxy compounds, thereby preparing a raw material mixture.
[0414] Next, the pressure in the glass reactor was reduced to 1.3-4.0 kPa (10-30 Torr), and then the operation of returning to atmospheric pressure with nitrogen was repeated 5 times to replace the interior of the reactor with nitrogen. After nitrogen replacement, the external temperature of the reactor was set to 220°C, and the internal temperature of the reactor was slowly raised to dissolve the mixture. Then, the stirrer was rotated at 100 rpm. Then, while distilling off the phenol produced as a by-product by the oligomerization reaction of the dihydroxy compound and DPC carried out inside the reactor, the pressure in the reactor was reduced from 101.3 kPa (760 Torr) to 13.3 kPa (100 Torr) by absolute pressure in 40 minutes.
[0415] Next, the pressure in the reactor was maintained at 13.3 kPa, and the ester exchange reaction was carried out for 80 minutes while further distilling and removing phenol. Then, the temperature outside the reactor was raised to 240°C, and the pressure inside the reactor was reduced from 13.3 kPa (100 Torr) to 399 Pa (3 Torr) by absolute pressure gauge in 40 minutes, and the distilled phenol was removed outside the system. Furthermore, the temperature outside the reactor was raised to 260°C, and the absolute pressure inside the reactor was reduced to 60 Pa (about 0.4 Torr) to carry out the polycondensation reaction. When the stirrer of the reactor reached the predetermined specified stirring power, the polycondensation reaction was terminated.
[0416] Next, the reactor was restored to an absolute pressure of 101.3 kPa using nitrogen gas, and then the pressure was increased to a gauge pressure of 0.2 MPa, and the polycarbonate resin was extracted from the bottom of the reactor in the form of strands. The obtained polycarbonate resin strands were cut into pellets using scissors.
[0417] The polycarbonate resin contains 27.7 wt % of carbonate structural units (X) and 72.3 wt % of carbonate structural units (Y), and has a biomass degree of 27.4 wt %.
[0418] The polycarbonate resin thus obtained was tested for Q value, glass transition temperature (Tg), and melting peak temperature (Tm), and then subjected to a heating test at 120° C. In addition, a tensile test was performed using a test piece obtained by hot pressing the polycarbonate resin to measure the tensile elastic modulus. In addition, a bending test of the hot pressing test piece was performed.
[0419] The results are shown in Table 5A.
[0420] [Example 8]
[0421] 58.36 g (about 0.0213 mol) of PO3G2700, 58.36 g (about 0.289 mol) of DHDE, 68.04 g (about 0.318 mol) of DPC and a 0.4 wt% aqueous solution of cesium carbonate as a catalyst were added so that the amount of cesium carbonate was 5 μmol per 1 mol of all dihydroxy compounds, and a raw material mixture was prepared, and the method described in Example 7 was used.
[0422] The obtained polycarbonate resin contained 47.2 wt % of carbonate structural units (X) and 52.8 wt % of carbonate structural units (Y), and had a biomass degree of 46.7 wt %.
[0423] The polycarbonate resin thus obtained was tested for Q value, glass transition temperature (Tg), and melting peak temperature (Tm), and then subjected to a heating test at 120° C. In addition, a tensile test was performed using a test piece obtained by hot pressing the polycarbonate resin to measure the tensile elastic modulus. In addition, a bending test of the hot pressing test piece was performed.
[0424] The results are shown in Table 5A.
[0425] [Example 9]
[0426] PO3G2700 70.03 g (about 0.0255 mol), DHDE 46.68 g (about 0.231 mol), DPC 56.57 g (about 0.264 mol) and a 0.4 wt% aqueous solution of cesium carbonate as a catalyst were added so that the amount of cesium carbonate was 5 μmol per 1 mol of all dihydroxy compounds, and a raw material mixture was prepared, and the method described in Example 7 was used.
[0427] The obtained polycarbonate resin contained 57.3 wt % of carbonate structural units (X) and 42.7 wt % of carbonate structural units (Y), and had a biomass degree of 56.7 wt %.
[0428] The polycarbonate resin thus obtained was tested for Q value, glass transition temperature (Tg), and melting peak temperature (Tm), and then subjected to a heating test at 120° C. In addition, a tensile test was performed using a test piece obtained by hot pressing the polycarbonate resin to measure the tensile elastic modulus. In addition, a bending test of the hot pressing test piece was performed.
[0429] The results are shown in Table 5A.
[0430] [Example 10]
[0431] PO3G2700 70.00 g (about 0.0259 mol), DHDE 30.00 g (about 0.148 mol), DPC 38.64 g (about 0.180 mol) and a 0.4 wt% aqueous solution of cesium carbonate as a catalyst were added so that the amount of cesium carbonate was 5 μmol per 1 mol of all dihydroxy compounds, and a raw material mixture was prepared, and the method described in Example 7 was used.
[0432] The obtained polycarbonate resin contained 67.6 wt % of carbonate structural units (X) and 32.4 wt % of carbonate structural units (Y), and had a biomass degree of 66.9 wt %.
[0433] The polycarbonate resin thus obtained was tested for Q value, glass transition temperature (Tg), and melting peak temperature (Tm), and then subjected to a heating test at 120° C. In addition, a tensile test was performed using a test piece obtained by hot pressing the polycarbonate resin to measure the tensile elastic modulus. In addition, a bending test of the hot pressing test piece was performed.
[0434] The results are shown in Table 5A.
[0435] [Example 11]
[0436] PO3G1000-2 35.01 g (about 0.0350 mol), DHDE 81.70 g (about 0.404 mol), DPC 94.99 g (about 0.443 mol) and a 0.4 wt% aqueous solution of cesium carbonate as a catalyst were added so that the amount of cesium carbonate was 5 μmol per 1 mol of all dihydroxy compounds, and a raw material mixture was prepared, and the method described in Example 7 was used.
[0437] The obtained polycarbonate resin contained 28.0 wt % of carbonate structural units (X) and 72.0 wt % of carbonate structural units (Y), and had a biomass degree of 27.3 wt %.
[0438] The polycarbonate resin thus obtained was tested for Q value, glass transition temperature (Tg), and melting peak temperature (Tm), and then subjected to a heating test at 120° C. In addition, a tensile test was performed using a test piece obtained by hot pressing the polycarbonate resin to measure the tensile elastic modulus. In addition, a bending test of the hot pressing test piece was performed.
[0439] The results are shown in Table 5A.
[0440] [Example 12]
[0441] 58.36 g (about 0.0584 mol) of PO3G1000-2, 58.36 g (about 0.289 mol) of DHDE, 75.44 g (about 0.352 mol) of DPC and a 0.4 wt% aqueous solution of cesium carbonate as a catalyst were added so that the amount of cesium carbonate was 5 μmol per 1 mol of all dihydroxy compounds, and a raw material mixture was prepared, and the method described in Example 7 was used.
[0442] The obtained polycarbonate resin contained 47.6 wt % of carbonate structural units (X) and 52.4 wt % of carbonate structural units (Y), and had a biomass degree of 46.4 wt %.
[0443] The polycarbonate resin thus obtained was tested for Q value, glass transition temperature (Tg), and melting peak temperature (Tm), and then subjected to a heating test at 120° C. In addition, a tensile test was performed using a test piece obtained by hot pressing the polycarbonate resin to measure the tensile elastic modulus. In addition, a bending test of the hot pressing test piece was performed.
[0444] The results are shown in Table 5A.
[0445] [Example 13]
[0446] PO3G2700 10.00 g (about 0.00365 mol), BPF 10.00 g (about 0.0499 mol), DPC 12.05 g (about 0.0563 mol) and a 0.4 wt% aqueous solution of cesium carbonate as a catalyst were added so that the amount of cesium carbonate was 5 μmol relative to 1 mol of all dihydroxy compounds, and a raw material mixture was prepared, and the method described in Example 7 was used.
[0447] The obtained polycarbonate resin contained 47.2 wt % of carbonate structural units (X) and 52.8 wt % of carbonate structural units (Y), and had a biomass degree of 46.7 wt %.
[0448] The polycarbonate resin thus obtained was tested for Q value, glass transition temperature (Tg), and melting peak temperature (Tm), and then subjected to a heating test at 120° C. In addition, a tensile test was performed using a test piece obtained by hot pressing the polycarbonate resin to measure the tensile elastic modulus. In addition, a bending test of the hot pressing test piece was performed.
[0449] The results are shown in Table 5A.
[0450] [Example 14]
[0451] 58.36 g (about 0.0213 mol) of PO3G2700, 58.36 g (about 0.267 mol) of ThioDP, 64.93 g (about 0.303 mol) of DPC and a 0.4 wt% aqueous solution of cesium carbonate as a catalyst were added so that the amount of cesium carbonate was 50 μmol relative to 1 mol of all dihydroxy compounds to prepare a raw material mixture, and the reaction was carried out at 240° C. without raising the external temperature of the reactor to 260° C., except that the reaction was carried out by the method described in Example 7.
[0452] The obtained polycarbonate resin contained 47.4 wt % of carbonate structural units (X) and 52.6 wt % of carbonate structural units (Y), and had a biomass degree of 46.9 wt %.
[0453] The polycarbonate resin thus obtained was tested for Q value, glass transition temperature (Tg), and melting peak temperature (Tm), and then subjected to a heating test at 120° C. In addition, a tensile test was performed using a test piece obtained by hot pressing the polycarbonate resin to measure the tensile elastic modulus. In addition, a bending test of the hot pressing test piece was performed.
[0454] The results are shown in Table 5A.
[0455] [Example 15]
[0456] 58.36 g (about 0.0213 mol) of PO3G2700, 58.36 g (about 0.256 mol) of BPA, 62.29 g (about 0.291 mol) of DPC and a 0.4 wt% aqueous solution of cesium carbonate as a catalyst were added so that the amount of cesium carbonate was 5 μmol per 1 mol of all dihydroxy compounds, and a raw material mixture was prepared, and the reaction was carried out according to the method described in Example 7.
[0457] The obtained polycarbonate resin contained 47.5 wt % of carbonate structural units (X) and 52.5 wt % of carbonate structural units (Y), and had a biomass degree of 47.1 wt %.
[0458] The polycarbonate resin thus obtained was tested for Q value, glass transition temperature (Tg), and melting peak temperature (Tm), and then subjected to a heating test at 120° C. In addition, a tensile test was performed using a test piece obtained by hot pressing the polycarbonate resin to measure the tensile elastic modulus. In addition, a bending test of the hot pressing test piece was performed.
[0459] The results are shown in Table 5A.
[0460] [Comparative Example 7]
[0461] The method described in Example 7 was used except that 116.71 g (about 0.511 mol) of BPA, 117.18 g (about 0.547 mol) of DPC and a 0.04 wt% aqueous solution of cesium carbonate as a catalyst were added so that the amount of cesium carbonate was 0.5 μmol relative to 1 mol of all dihydroxy compounds to prepare a raw material mixture, and the external temperature of the reactor after heating from 220° C. was changed from 240° C. to 290° C. and the reaction was carried out at 290° C. until the polymerization was completed.
[0462] The obtained polycarbonate resin consisted of 100 wt % of carbonate structural units (Y) and had a biomass content of 0 wt %.
[0463] The polycarbonate resin thus obtained was tested for Q value, glass transition temperature (Tg), and melting peak temperature (Tm), and then subjected to a heating test at 120° C. In addition, a tensile test was performed using a test piece obtained by hot pressing the polycarbonate resin to measure the tensile elastic modulus. In addition, a bending test of the hot pressing test piece was performed.
[0464] The results are shown in Table 5B.
[0465] [Comparative Example 8]
[0466] 58.36 g (about 0.0151 mol) of PTMG4000, 58.36 g (about 0.289 mol) of DHDE, 66.69 g (about 0.311 mol) of DPC and a 0.4 wt% aqueous solution of cesium carbonate as a catalyst were added so that the amount of cesium carbonate was 5 μmol per 1 mol of all dihydroxy compounds, and a raw material mixture was prepared, and the reaction was carried out according to the method described in Example 7.
[0467] The obtained polycarbonate resin contained 47.1 wt % of other carbonate structural units (X) and 52.9 wt % of carbonate structural units (Y), and the biomass degree was 0 wt %.
[0468] The polycarbonate resin thus obtained was tested for Q value, glass transition temperature (Tg), and melting peak temperature (Tm), and then subjected to a heating test at 120° C. In addition, a tensile test was performed using a test piece obtained by hot pressing the polycarbonate resin to measure the tensile elastic modulus. In addition, a bending test of the hot pressing test piece was performed.
[0469] The results are shown in Table 5B.
[0470] [Comparative Example 9]
[0471] 99.20 g (about 0.176 mol) of PO3G500-1, 17.51 g (about 0.0767 mol) of BPA, 58.04 g (about 0.271 mol) of DPC and a 0.4 wt% aqueous solution of cesium carbonate as a catalyst were added so that the amount of cesium carbonate was 4.9 μmol per 1 mol of all dihydroxy compounds, and a raw material mixture was prepared, and the reaction was carried out according to the method described in Example 7.
[0472] The obtained polycarbonate resin contained 84.2 wt % of carbonate structural units (X) and 15.8 wt % of carbonate structural units (Y), and had a biomass degree of 80.2 wt %.
[0473] The polycarbonate resin thus obtained was measured for Q value, glass transition temperature (Tg), and melting peak temperature (Tm), and further subjected to a heating test at 120° C. Since the polycarbonate resin does not cure at room temperature, it could not be hot pressed, and a tensile test or a bending test could not be performed.
[0474] The results are shown in Table 5B.
[0475] [Table 5A]
[0476]
[0477] [Table 5B]
[0478]
[0479] [Examination of Examples 7 to 15 and Comparative Examples 7 to 9]
[0480] The results of Examples 7 to 15 and Comparative Examples 7 to 9 reveal the following.
[0481] As can be seen from Table 5A, Examples 7 to 15 contain carbonate structural units (X) of PO3G and carbonate structural units (Y) of dihydroxy compounds (2), and have melting point peak temperatures, so low-temperature mechanical strength (glass transition temperature), heat resistance, flexibility, and mechanical strength are all good results.
[0482] Comparative Example 7 in Table 5B is a common BPA polycarbonate resin and has poor flexibility.
[0483] Comparative Example 2 using PTMG instead of PO3G was inferior in mechanical strength.
[0484] Comparative Example 3, which has carbonate structural units (X) and carbonate structural units (Y) but has an excessively large content of carbonate structural units (X), has no melting point peak temperature, is poor in heat resistance, and does not solidify at room temperature, so that press processing is impossible.
[0485] [Example 16]
[0486] 50 wt % of each of the polycarbonate resin produced in Example 2 (biomass degree = 57.7 wt %) and the polycarbonate resin produced in Example 3 (biomass degree = 67.8 wt %) were dry-blended to obtain a polycarbonate resin composition (biomass degree = 62.7 wt %).
[0487] The glass transition temperature (Tg) and melting peak temperature (Tm) of the polycarbonate resin composition were measured, and a heating test was further performed at 120° C. In addition, a tensile test was performed using a test piece obtained by hot pressing the polycarbonate resin composition to measure the tensile elastic modulus and elongation at break. In addition, a bending test of the hot pressing test piece was performed.
[0488] The results are shown in Table 6.
[0489] [Table 6]
[0490]
[0491] As can be seen from Table 6, even when two or more polycarbonate resins of the present invention are blended, excellent heat resistance, flexibility, mechanical strength, and low-temperature mechanical strength can be obtained.
[0492] [Investigation]
[0493] The reason why the polycarbonate resins of Examples can achieve both particularly excellent heat resistance and flexibility is considered as follows.
[0494] For the polycarbonate resin composition of the present invention having a carbonate structural unit (X) and a carbonate structural unit (Y) and having a melting point peak temperature, it is considered that the carbonate structural unit (X) becomes a soft segment, the carbonate structural unit (Y) becomes a hard segment, and the hard segment is quasi-crosslinked, so it exhibits high heat resistance, and flexibility can also be imparted by the soft segment.
[0495] From the above results, it is understood that the polycarbonate resin composition of the present invention is excellent in heat resistance, flexibility, mechanical strength, low-temperature mechanical strength, and rubber elasticity.
[0496] Although the present invention has been described in detail using specific embodiments, it is apparent to those skilled in the art that various modifications can be made within the scope of achieving the effects of the invention.
[0497] This application is based on Japanese Patent Application No. 2022-120723 and Japanese Patent Application No. 2022-120724 filed on Jul. 28, 2022, the entireties of which are incorporated herein by reference.
Claims
1. A polycarbonate resin composition comprising a carbonate structural unit (X) derived from an aliphatic dihydroxy compound (1) represented by the following formula (1) and a carbonate structural unit (Y) derived from a dihydroxy compound (2) satisfying the following requirement 1, The polycarbonate resin composition has a melting point peak temperature when the melting point peak temperature is measured by heating at a temperature increase rate of 20° C. / min using a differential scanning calorimeter. <Requirement I> The polycarbonate resin (2) obtained by polymerizing the dihydroxy compound (2) and a carbonate source by an ester exchange method has a melting point peak temperature when the melting point peak temperature is measured by heating at a heating rate of 20° C. / min using a differential scanning calorimeter. [Chemistry 1] In formula (1), n is an integer of 2 or more.
2. The polycarbonate resin composition according to claim 1, wherein the content of the carbonate structural unit (X) is greater than 1 wt % and less than 99 wt %, and the content of the carbonate structural unit (Y) is greater than 0.1 wt % and less than 99 wt %, in 100 wt % of all carbonate structural units in the polycarbonate resin composition.
3. The polycarbonate resin composition according to claim 2, wherein the content of the carbonate structural unit (X) is greater than 1 wt % and less than 75 wt %, and the content of the carbonate structural unit (Y) is greater than 25 wt % and less than 99 wt %, in 100 wt % of all carbonate structural units in the polycarbonate resin composition. 4 . The polycarbonate resin composition according to claim 1 , wherein the sum of the content of the carbonate structural unit (X) and the content of the carbonate structural unit (Y) in 100 wt % of all carbonate structural units in the polycarbonate resin composition is 90 wt % or more. 5 . The polycarbonate resin composition according to claim 1 , wherein the aliphatic dihydroxy compound represented by formula (1) has a number average molecular weight of 400 or more and 2,900 or less.
6. The polycarbonate resin composition according to claim 1, wherein in the measurement of the melting point peak temperature of the requirement 1, when the polycarbonate resin (2) obtained by polymerization by an ester exchange method is directly subjected to the measurement of the melting point peak temperature, the polycarbonate resin (2) has a melting point peak temperature. 7 . The polycarbonate resin composition according to claim 1 , wherein the polycarbonate resin (2) has a melting point peak temperature of 150° C. or higher and 300° C. or lower.
8. The polycarbonate resin composition according to claim 1, wherein the dihydroxy compound (2) is a dihydroxy compound represented by any one of the following formulas (2) to (6): [Chemistry 2] 9 . The polycarbonate resin composition according to claim 1 , wherein the polycarbonate resin composition has the melting point peak temperature in the range of 150° C. or higher. 10 . The polycarbonate resin composition according to claim 1 , wherein the polycarbonate resin composition has the melting point peak temperature in a range of 240° C. or less.
11. The polycarbonate resin composition according to claim 1, wherein the dihydroxy compound (2) is a dihydroxy compound represented by the following formula (2): [Chemistry 3] 12 . The polycarbonate resin composition according to claim 11 , wherein the number average molecular weight Mn (i.e., polystyrene-equivalent molecular weight) measured by GPC is 10,000 to 100,000. 13 . The polycarbonate resin composition according to claim 1 , comprising the carbonate structural unit (X) and the carbonate structural unit (Y) in the form of a copolymerized polycarbonate resin. 14 . The polycarbonate resin composition according to claim 1 , which is a blend of a polycarbonate resin comprising the carbonate structural unit (X) and a polycarbonate resin comprising the carbonate structural unit (Y).
15. The polycarbonate resin composition according to claim 1, wherein the Q value measured by a high-performance rheometer at 240°C and 160 kgf is 3×10 -2 cm 3 / sec or more. 16 . The polycarbonate resin composition according to claim 1 , which has a glass transition temperature of 30° C. or less when the glass transition point is measured by heating at a temperature increase rate of 20° C. / min using a differential scanning calorimeter. 17 . The polycarbonate resin composition according to claim 1 , wherein a sample obtained by hot pressing has a tensile elastic modulus of 5 MPa to 300 MPa. 18 . A thermoplastic resin composition comprising the polycarbonate resin composition according to claim 1 , wherein a content of the polycarbonate resin composition in 100 wt % of the thermoplastic resin composition is 1 wt % or more and 30 wt % or less. 19 . An injection-molded article obtained by injection-molding the polycarbonate resin composition according to claim 1 or the thermoplastic resin composition according to claim 18 . 20 . An extrusion-molded article obtained by extrusion-molding the polycarbonate resin composition according to claim 1 or the thermoplastic resin composition according to claim 18 . The extrusion-molded product according to claim 20 , which is a sheet or a film.
Citation Information
Patent Citations
Polycarbonate resin, and polycarbonate resin composition
JP2021091900A
Copolymerized polycarbonate resin, and heat storage material and heat storage molded body containing the same
JP2021169606A
Control device, program, and control method
JP2022120723A
Hydroponic device with low water-level adjustment mechanism
JP2022120724A
Polycarbonate and process for producing the same
WO2004111106A1